Orbital imaging spectroscopy of Earth’s mineral surface: Results and stability from EMIT’s first two years - Marie-Stephane Guillaumont; David R. Thompson; Philip G. Brodrick; Roger Clark; Robert O. Green; Gregory S. Okin (Remote Sensing of Environment, 2026)

Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Leveraging EMIT spectroscopy and machine learning to estimate soil texture and particle grain size in dust-producing regions - Gregory S. Okin; Bo Zhou; Philip G. Brodrick; Francisco Ochoa; María Gonçalves Ageitos; Roger N. Clark; Michael R. Fischella; Carlos Pérez García-Pando; Longlei Li; Natalie Mahowald; David R. Thompson; Robert O. Green (Remote Sensing of Environment, 2026)

Misspecification of the generation time distribution and its impact on Rt estimates in structured populations - Ioana Bouros; Robin N. Thompson; David Gavaghan; Ben Lambert (Journal of Theoretical Biology, 2026)

Mercury concentrations in cephalopods from the Pacific sector of the Southern Ocean in relation to their biology, habitat and trophic position - Marius Lespinas; José C. Xavier; Paco Bustamante; José P. Queirós; David R. Thompson; Pedro Coelho; Maria Eduarda Pereira; José Seco (Marine Environmental Research, 2026)

Ecological and genetic determinants of essential oil diversity in Mediterranean Thymus - José C. del Valle; Esther María Martín-Carretié; Francisco José García-Cárdenas; David Doblas; María Ángeles Ortiz; John Thompson; Perrine Gauthier; Bodil K. Ehlers; Diego Nieto-Lugilde; Regina Berjano (Biochemical Systematics and Ecology, 2026)

Mountain waves, downslope jets, and boundary layer interactions during the Sundowner Winds Experiment (SWEX) - IOP2 - Daisuke Seto; Leila M.V. Carvalho; Gert-Jan Duine; Stephan De Wekker; Zhien Wang; Charles Jones; David Emmitt; Steve Greco; Harindra J.S. Fernando; Griffin Modjeski; Craig B. Clements; Marian de Orla-Barile; et al. (Atmospheric Research, 2026)

Meet me in the middle: potential collaborative benthic hunting in humpback whales (Megaptera novaeangliae) - David N. Wiley; David E. Cade; Ari S. Friedlaender; Jeremy Goldbogen; Jessica Kendall-Bar; Susan E. Parks; Michael A. Thompson; Mason Weinrich; Tammy L. Silva (Behavioral Ecology and Sociobiology, 2026)
Cooperative hunting, in its numerous forms, has implications for animal cognition and social evolution. We used multi-sensor acoustic/video recording tags attached to free-swimming humpback whales (Megaptera novaeangliae) to provide the species’ first documentation of cooperative, coordinated benthic hunting and evidence supporting collaboration, the most cognitively complex level of hunting. Collaborative hunting, consisting of the tagged whale and 1–3 co-hunters, comprised 79% ( n = 110) of observed benthic-hunting events. Hunting animals concurrently arrived at the seafloor and simultaneously moved towards co-hunters, forming a head-to-head configuration that terminated when rostrums were within meters of each other; a behavior that could be seen to drive/corral sand lance ( Ammodytes dubius ) prey towards co-hunter(s). Tagged animals changed their direction of attack for each event, but co-hunters typically realigned into the same relative position, based on that of co-hunters. Using a clock position method, in relation to the tagged animal’s heading (12:00; n = 87), co-hunters occupied the 1:00 position most frequently (59%), followed by 11:00 (35%), 12:00 (12%), 3:00 (5%), and 2:00 (2%). The 1:00 and 11:00 locations would be optimal prey herding/capture positions. In events where all co-hunters were identified, individuals assumed the same position in 93.1% of events ( n = 54). Animals opened their mouths for prey capture in near unison (mean offset 3.7 s, SD 5.3 s, n = 43). The fission-fusion, non-kin-based social system of humpback whales makes them an unlikely species to evolve collaborative hunting. We speculate that the need to capture small, evasive prey, combined with cognitively driven behavioral plasticity contribute to the evolution of this hunting strategy.

Memes as Structural Signals: A Chemical Model of Interpretive Compatibility - Eric Gladstone; David C. Thompson (Biosemiotics, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Will there ever be an in vitro assay that is predictive for human hepatotoxicity? - David C. Thompson (Archives of Toxicology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Development and validation of matrix-validated LC–MS/MS method for simultaneous quantification of 21 neonicotinoids and their metabolites in human urine - Wenjing Xi; Sarah Onysio; Mary C. Rhodes; Alexis J. Faudel; John C. Flunker; Mark K. Santillan; Donna A. Santillan; David M. Cwiertny; Darrin A. Thompson (Environmental Science and Pollution Research, 2026)
Neonicotinoids (NEOs) are the most widely used class of insecticides worldwide. Consequently, human exposure occurs through multiple pathways, including dietary intake and environmental contact. Previous analytical methods have primarily focused on parent compounds, often excluding key metabolites due to matrix effects and poor quantification in complex biological samples. This gap severely limits the ability to accurately assess total NEO exposure and internal dose, highlighting the urgent need for more comprehensive and reliable biomonitoring approaches. This study developed a comprehensive LC–MS/MS method to quantify 21 NEOs and metabolites in human urine, uniquely including key transformation products such as clothianidin-n-desmethyl, clothianidin-urea, imidacloprid-urea, imidacloprid-olefin, 5-hydroxy-imidacloprid, thiamethoxam-urea, and thiamethoxam-n-desmethyl, thereby enabling a more thorough assessment of human exposure to NEOs. The method was validated using both synthetic and pooled human urine, providing a critical assessment of matrix-dependent variations in detection limits, accuracy, and precision. Method performance demonstrated high sensitivity, specificity, accuracy, and precision, with limits of quantification (LOQ) from 0.017 to 0.46 ng/mL and limits of detection (LOD) from 0.0050 to 0.14 ng/mL. The method was applied to urine samples from 246 pregnant women and 47 farmers in eastern Iowa to assess exposure levels. Results indicated widespread NEO exposure with detection frequencies of 99% of pregnant women and 100% in farmers, with 18 different NEOs and metabolites detected across both populations. Metabolite monitoring revealed that imidacloprid metabolites (IMI-O, 5-OH-IMI) were stronger predictors of total neonicotinoid burden than parent compounds alone ( r s = 0.735 vs < 0.6 for parents), with some metabolites showing higher concentrations in pregnant women than farmers despite farmers having higher overall exposure. These findings demonstrate that parent-only biomonitoring substantially underestimates internal neonicotinoid exposure and fails to capture critical exposure pathways, particularly for vulnerable populations where metabolite patterns may differ significantly from occupational exposure profiles.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Investigating the contributions of herbaceous vegetation biomass to soil accretion in Louisiana's coastal deltaic wetlands using airborne imaging spectroscopy - Daniel Jensen; Elena Solohin; Edward Castañeda-Moya; Marc Simard; David R. Thompson; Cathleen E. Jones; Alexandra Christensen; Andre Rovai; Andy Fontenot; Robert Twilley (Remote Sensing of Environment, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Delta-X: An airborne remote sensing framework to calibrate hydrodynamic and ecogeomorphic processes responsible for land building in coastal deltas - Marc Simard; Cathleen E. Jones; Robert R. Twilley; Edward Castañeda-Moya; Sergio Fagherazzi; Cédric G. Fichot; Michael P. Lamb; Paola Passalacqua; Tamlin M. Pavelsky; David R. Thompson; Saoussen Belhadj-aissa; Pradipta Biswas; et al. (Remote Sensing of Environment, 2026)

Differential effects of adolescent fatty acid amide hydrolase and monoacylglycerol lipase inhibition on adolescent and adult behaviors in male rats - Mary K. Estes; Vishnu Guda; Emei Thompson; Daniela Rodrigues de Oliveira; David B. Nowak; Cecilia J. Hillard; John R. Mantsch (Psychopharmacology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Undergraduate students’ career goals and perceptions of urban forestry in Historically Black Colleges and Universities - Yujuan Chen; De’Etra Young; Aria McElroy; Reginald Archer; David Padgett; Alton Thompson (Urban Forestry & Urban Greening, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

Satellite observations reveal ecosystem resistance and resilience to short-term water stress driven by dominant vegetation along a rainfall gradient in Australia - Huanhuan Wang; Qiaoyun Xie; Sally E. Thompson; Caitlin E. Moore; David L. Miller; Erik J. Veneklaas; Richard P. Silberstein; Xing Li; Jingfeng Xiao; Belinda E. Medlyn; William K. Smith (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Military-Related Weight Stigma Prospectively Predicts Dietary Restraint During Pregnancy in US Military Active-Duty Service Members: A Longitudinal Observational Study - Katherine A. Thompson; Viviana Bauman; Ruby Schrag; Marney A. White; Autumn Mains; Stephanie Rioux; Holly Spinner; Isabel Thorstad; Victoria Thomas; David Klein; Mark Haigney; Marian Tanofsky-Kraff; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

High frequency DOC proxy sensor assessment for peatland streams and across hydrological continua - Hannah Thompson; Joerg Arnscheidt; Hugo McGrogan; David P. Ryan; Phil Jordan (Journal of Environmental Management, 2025)

Combining magnetotelluric, DC resistivity, and time-domain electromagnetic data in geothermal exploration: An example from the M’Deek Geothermal Field in Western British Columbia, Canada - Zoë Vestrum; Martyn J Unsworth; Tim Thompson; David Try (Geothermics, 2025)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Environmental and socio-economic Pareto-front trade-off analysis of U.S. PET packaging material in a circular economy - Utkarsh S. Chaudhari; David W. Watkins; Robert M. Handler; Barbara K. Reck; Anne T. Johnson; Tasmin Hossain; Damon S. Hartley; Vicki S. Thompson; David R. Shonnard (Sustainable Production and Consumption, 2025)

Serum Biomarkers in Atlantic Salmon for Differential Diagnosis of Cardiomyopathy Syndrome and Pancreas Disease: Proteomic Identification of Serum Fibrinogen to Enhance Troponin Immunoassay as Optimal Diagnostic Approach - Francesca Riva; Lauren Elaine Black; Kim D. Thompson; Philippe Sourd; Andrei Bordeianu; Christopher C. Chadwick; Hooman Moghadam; Jorge Del‐Pozo; Janina Costa; Richard Burchmore; Nicola Brady; Lewis Moore; et al. (Journal of Fish Diseases, 2025)
Cardiac viral diseases are among the major causes of economic losses in Atlantic salmon ( Salmo salar L.) aquaculture. These include cardiomyopathy syndrome (CMS) caused by piscine myocarditis virus (PMCV) and pancreas disease (PD) caused by Atlantic salmonid alphavirus (SAV). The resulting cardiomyopathies impact fish stock in terms of mortality, quality, growth performance and economic loss. Diagnosis of these diseases is currently based on clinical signs, histopathology and RT‐qPCR. To identify putative biomarkers for use in the health assessment of Atlantic salmon, a quantitative proteomics investigation was undertaken with the aim of differentiating fish with CMS from healthy fish and fish with PD. Serum samples ( n = 9/group) were collected during health assessment from pens where clinical CMS or PD were present and compared to serum from healthy Atlantic salmon. There were 34 differentially abundant proteins (DAPs) in CMS compared to healthy, 66 comparing CMS to PD, and 81 comparing PD to healthy. In relation to healthy samples, most DAPs were shared between CMS and PD, with higher relative abundances observed in PD. An exception to this was serum fibrinogen, which was identified as a putative biomarker for CMS, whereas differentiation of Atlantic salmon with CMS from those with PD was enhanced by the calculation of the ratio of fibrinogen to skeletal troponin C.

Identification of false methane plumes for orbital imaging spectrometers: A case study with EMIT - Chuchu Xiang; David R. Thompson; Robert O. Green; Jay E. Fahlen; Andrew K. Thorpe; Philip G. Brodrick; Red Willow Coleman; Amanda M. Lopez; Clayton D. Elder (Remote Sensing of Environment, 2025)

Revealing fundamental demand parameters: A new theoretically consistent meta-regression approach to US food demand elasticities - Younghyeon Jeon; Wyatt Thompson; J. Isaac Miller; Hoa Hoang; David Abler (Food Policy, 2025)

Fast-start performance and its dependence on temperature and salinity in sheepshead minnow (Cyprinodon variegatus) - David C. Collar; Kayla L. Stanley; Jessica S. Thompson (Environmental Biology of Fishes, 2025)
Estuarine fishes regularly experience fluctuations in water temperature and salinity, and many species exhibit broad tolerances that allow them to withstand extreme conditions without mortality. However, a full understanding of physiological capacities that permit occupancy of such changeable habitats also requires insight into how organismal performance responds to environmental variation. In this study, we evaluated fast-start escape performance of sheepshead minnow ( Cyprinodon variegatus ), a noted eurythermal and euryhaline estuary-resident, across temperatures near the warm extreme of its thermal range (24, 30, 36 °C) and salinities varying from low to hypersaline (2, 32, 52 ppt). Fast-start speeds were directly related to the temperature at which fish were tested, but they also exhibited dependence on acclimation conditions. Angular velocity of the initial C-bend was faster at higher test temperatures, but at any given temperature, rotation was fastest in fish held at lower temperatures and at intermediate or high salinities. While temperature and salinity effects were detectable, they were modest in magnitude. These results suggest that sheepshead minnow fast-start performance is relatively robust to environmental variability but can be influenced by fluctuating conditions within estuaries. Short-term increases in temperature brought on by daily tidal cycles may lead to elevated fast-start speeds, but long-term exposure to high temperatures (predicted to increase given climate change) or low salinities (resulting from rainwater inundation of marshes) may contribute to a reduction in fast-start performance and potentially increased vulnerability to predators.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Beta-Amino Carboxylate (BAC) non-aqueous physical solvents for enhanced CO2 separations in pre-combustion carbon capture, industrial CO2 capture, and biogas upgrading processes - Jeffrey T. Culp; Robert L. Thompson; Kathryn H. Smith; David Hopkinson; Nicholas Siefert (International Journal of Greenhouse Gas Control, 2025)

Assessing the Effectiveness of 3D-Printed Ceramic Structures for Coral Restoration: Growth, Survivorship, and Biodiversity Using Visual Surveys and eDNA - Vriko Yu; Alison D. Corley; Horace Lau; Philip D. Thompson; Zhongyue Wilson Wan; Jane C. Y. Wong; Zoe Kwan Ting Wong; Louise Wai Hung Li; Shelby E. McIlroy; David M. Baker (Journal of Marine Science and Engineering, 2025)
Coral reef degradation has spurred the development of artificial structures to mitigate losses in coral cover. These structures serve as substrates for coral transplantation, with the expectation that growing corals will attract reef-associated taxa—while the substrate’s ability to directly support biodiversity is often neglected. We evaluated a novel 3D-printed modular tile made of porous terra cotta, designed with complex surface structures to enhance micro- and cryptic biodiversity, through a restoration project in Hong Kong. Over four years, we monitored 378 outplanted coral fragments using diver assessments and photography, while biodiversity changes were assessed through visual surveys and eDNA metabarcoding. Coral survivorship was high, with 88% survival after four years. Visual surveys recorded seven times more fish and almost 60% more invertebrates at the restoration site compared to a nearby unrestored area. eDNA analyses revealed a 23.5% higher eukaryote ASV richness at the restoration site than the unrestored site and 13.3% greater richness relative to a natural reference coral community. This study highlights the tiles’ dual functionality: (1) supporting coral growth and (2) enhancing cryptic biodiversity, an aspect often neglected in traditional reef restoration efforts. Our findings underscore the potential of 3D-printed ceramic structures to improve both coral restoration outcomes and broader reef ecosystem recovery.

Integrating the Maximum Entropy Production model and airborne imagery for understorey evapotranspiration mapping - Wenjie Liu; Okke Batelaan; David Bruce; Jingfeng Wang; Hugo Gutierrez; Hailong Wang; Robin Keegan-Treloar; Jianfeng Gou; Robert Keane; Jessica Thompson; Huade Guan (Journal of Hydrology, 2025)

Soil and vegetation cover estimation for global imaging spectroscopy using spectral mixture analysis - Francisco Ochoa; Philip G. Brodrick; Gregory S. Okin; Eyal Ben-Dor; Thoralf Meyer; David R. Thompson; Robert O. Green (Remote Sensing of Environment, 2025)

Effect of baseplate flexibility and rail pad stiffness on slab track dynamics - Xianying Zhang; David J. Thompson; Evangelos Ntotsios; Boniface Hima; Giacomo Squicciarini (Engineering Structures, 2025)

Publisher Correction: Investigation of blood–brain barrier penetration and pharmacokinetics of a new formulation of cyanide antidote dimethyl trisulfide - Lóránd Kiss; Fruzsina R. Walter; Gábor Katona; Ana Raquel Santa-Maria; Ashley C. Whiteman; Christian T. Rios; Kyler D. Kelley; Breanna Nelson; David E. Thompson; Ildikó Csóka; Piroska Szabó-Révész; Mária A. Deli; et al. (Toxicology and Environmental Health Sciences, 2025)

Investigation of blood–brain barrier penetration and pharmacokinetics of a new formulation of cyanide antidote dimethyl trisulfide - Lóránd Kiss; Fruzsina R. Walter; Gábor Katona; Ana Raquel Santa-Maria; Ashley C. Whiteman; Christian T. Rios; Kyler D. Kelley; Breanna Nelson; David E. Thompson; Ildikó Csóka; Piroska Szabó-Révész; Mária A. Deli; et al. (Toxicology and Environmental Health Sciences, 2025)
Objective During cyanide poisoning, the rescue of vital organs like the brain is urgent. However, due to the presence of the blood–brain barrier (BBB), the currently available cyanide antidotes cannot reach the brain. Dimethyl trisulfide (DMTS) is a potent cyanide antidote and has excellent BBB permeability. Nonetheless, its formulation and application are challenging due to its highly lipophilic profile. In this work, a novel DMTS formulation, called FF-DMTS, was investigated. Its effect on in vitro DMTS permeability through BBB models, cellular viability, and in vivo absorption were tested. Methods The particle size was measured in FF-DMTS formulation. The permeability of DMTS in this new formulation was tested in BBB-PAMPA and in primary triple co-culture models of BBB. The effect of FF-DMTS on cellular viability was determined. To test the membrane and barrier integrity transendothelial electrical resistance (TEER) and cell layer impedance measurements, immunofluorescent stainings and the fluorescein permeability technique were applied. The pharmacokinetics of DMTS were revealed in blood and brain tissue. Results The average size of micelles in FF-DMTS was 16 nm. The permeability of DMTS through BBB-PAMPA and cell culture model was 7.68 × 10 –6 and 23.81 × 10 –6 cm/s, respectively. The FF-DMTS disturbed the barrier integrity of brain endothelial cells without causing any alteration in cellular viability until 300 µg/ml DMTS concentration. After administration of 150 mg/kg DMTS to mice, its absorption into the blood was rapid (5 min) and the plasma concentration of DMTS reached 5.2 µg/ml. The DMTS was also detected in brain, where its peak concentration was 495 ng/g brain tissue after 10 min of intramuscular administration. Furthermore, even 2 h later, DMTS was detected in brain. Conclusions Here, we showed that the novel FF-DMTS formulation has good permeability through BBB and a remarkable pharmacokinetic profile. Therefore, further investigation of the efficacy of FF-DMTS for treating cyanide intoxication is important.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The Multifractal Gaussian Mixture Model for unsupervised segmentation of complex data sets - Garry Jacyna; Damon Frezza; David M. Slater; James R. Thompson (Spatial Statistics, 2025)

Modeling the impacts of sand placement strategies on barrier island evolution in a semi-enclosed bay system - Davina L. Passeri; Rangley C. Mickey; David M. Thompson; Michael Itzkin; Elizabeth Godsey; Matthew V. Bilskie; Alexander Seymour; Autumn Poisson; Jin Ikeda; Scott C. Hagen (Coastal Engineering, 2025)

Pan-Canadian Predictive Modeling of Lithium–Cesium–Tantalum Pegmatites with Deep Learning and Natural Language Processing - Mohammad Parsa; Christopher J. M. Lawley; Tarryn Cawood; Tania Martins; Renato Cumani; Steven E. Zhang; Aaron Thompson; Ernst Schetselaar; Steve Beyer; David R. Lentz; Jeff Harris; Hossein Jodeiri Akbari Fam; et al. (Natural Resources Research, 2025)
The discovery of new lithium resources is essential because lithium plays a vital role in the manufacturing of green technology. Along with brines and volcano–sedimentary deposits, approximately a one-third share of global lithium resources is associated with lithium-cesium-tantalum (LCT) pegmatites, with Canada hosting numerous examples. This research applied generative adversarial networks, natural language processing, and convolutional neural networks to generate mineral prospectivity models and support exploration targeting for Canadian LCT pegmatites. Geoscientific text data included within public bedrock geology maps and natural language processing were used to convert conceptual targeting criteria into evidence layers that complement more traditional, geophysical and geochronological data used for mineral prospectivity modeling (MPM). A multilayer architecture of convolutional neural networks, including an attention mechanism, was designed for data modeling. This architecture was trained and validated using variable synthetically generated class labels, input image sizes, and hyperparameters, resulting in an ensemble of 1000 models. The uncertainty of the ensemble was analyzed using a risk–return analysis, yielding a bivariate choropleth risk–return plot that facilitates the interpretation of prospectivity models for downstream applications. This was further complemented by employing post hoc interpretability algorithms to translate the black-box nature of neural networks into comprehensible content. The low-risk and high return class of our prospectivity models reduces the search space for discovering LCT pegmatites by 88%, delineating 99% of known LCT pegmatites in Canada. The results of this study suggest that our workflow (i.e., combining synthetic data generation, natural language processing, convolutional neural networks, and uncertainty propagation for MPM) facilitates decision-making for regional-scale lithium exploration and could also be applied to other mineral systems.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Evidence of eastern rockhopper penguin feeding on a key commercial arrow squid species - Hugo R. Guímaro; David R. Thompson; Kyle W. Morrison; Joana Fragão; Ricardo S. Matias; José C. Xavier (Polar Biology, 2025)
Cephalopods are crucial to the Southern Ocean ecosystem, connecting top predators with mid-trophic organisms, yet their ecology in the Pacific sector is not well understood. This research used stable isotope analysis to explore the habitat and trophic ecology of cephalopods found in the diet of eastern rockhopper penguins ( Eudyptes chrysocome filholi ) around Campbell Island, a New Zealand sub-Antarctic island. Eastern rockhopper penguins were used as biologic samplers, revealing some differences in cephalopod diversity and ecology between two breeding seasons—1986–87 and 2012–13—, and the squid Nototodarus sloanii , a commercially valuable species, was described for the first time in the 2012–13 season. Stable isotope values ( δ 13 C and δ 15 N) for the squid species Moroteuthopsis ingens were consistent between seasons, indicating ecological stability, whereas the octopod species Octopus campbelli showed changes, suggesting shifts in habitat and feeding. Warmer oceanic temperatures in 2012–13 may have facilitated the emergence of N. sloanii on the diet of the eastern rockhopper penguins. These findings highlight potential changes in cephalopod biodiversity in the Pacific sector of the Southern Ocean, emphasizing the need for further research on ecological dynamics of this region.

Impacts of climate change on storm event-based flow regime and channel stability of urban headwater streams - Sami Towsif Khan; David J. Sample; Theresa Wynn-Thompson; Jon Butcher (Journal of Environmental Management, 2025)

Nanoscale reservoirs store solar wind-derived water on the lunar surface - Alexander M. Kling; Jennika Greer; Michelle S. Thompson; Philipp R. Heck; Dieter Isheim; David N. Seidman (Earth and Planetary Science Letters, 2025)

Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Epilithic algal composition and the functioning of Anthropocene coral reefs - Sterling B. Tebbett; Michael J. Emslie; Michelle J. Jonker; Scott D. Ling; Morgan S. Pratchett; Alexandre C. Siqueira; Angus A. Thompson; Helen F. Yan; David R. Bellwood (Marine Pollution Bulletin, 2025)

The effects of carbonate contamination on Ni-Cu-PGE deposit genesis in the Platreef, northern Bushveld Complex: A case study using Niggli numbers - Erin S. Thompson; David A. Holwell; Iain McDonald; Marc Reichow; Thomas G. Blenkinsop; Hannah S.R. Hughes; Katie McFall; Kate R. Canham; Matthew A. Loader; Lara Du Preez; Kofi Acheampong; Andy Lloyd (Chemical Geology, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Development and preliminary validation of a modified Food Craving Inventory for Pregnancy (FCI-P) in U.S. military active-duty Service women - Katherine Thompson; Marney A. White; Ruby Schrag; Jason M. Lavender; Viviana Bauman; Autumn Mains; Stephanie Rioux; Holly Spinner; Isabel Thorstad; David Klein; Mark Haigney; Marian Tanofsky-Kraff (Appetite, 2024)

Small volume solid phase extraction method for comprehensive analysis of neonicotinoids, their metabolites, and related pesticides in water - Wenjing Xi; Sarah Onysio; James Kacer; Matthew Nagorzanski; Hanseob Shin; David M. Cwiertny; Darrin A. Thompson (Science of The Total Environment, 2024)

An accuracy assessment of the surface reflectance product from the EMIT imaging spectrometer - Red Willow Coleman; David R. Thompson; Philip G. Brodrick; Eyal Ben Dor; Evan Cox; Carlos Pérez García-Pando; Todd Hoefen; Raymond F. Kokaly; John M. Meyer; Francisco Ochoa; Gregory S. Okin; Daniela Heller Pearlshtien; et al. (Remote Sensing of Environment, 2024)

Using geophysical subsurface data for the reconstruction of valley-scale spatio-temporal floodplain evolution: Implications for upland river restoration - Arved C. Schwendel; David J. Milan; Richard J.J. Pope; Richard Williams; Warren Thompson (Geomorphology, 2024)

The cost of operational complexity: A causal assessment of pre-fire mitigation and wildfire suppression - Jesse D. Young; Erin Belval; Benjamin Gannon; Yu Wei; Christopher O'Connor; Christopher Dunn; Bradley M. Pietruszka; David Calkin; Matthew Thompson (Forest Policy and Economics, 2024)

Perspectives on the quality of climate information for adaptation decision support - Marina Baldissera Pacchetti; Suraje Dessai; James S. Risbey; David A. Stainforth; Erica Thompson (Climatic Change, 2024)
We summarise the contributions to the Topical Collection on quality of climate information for adaptation decision support. Based on these contributions, we draw some further lessons for the development of high-quality climate information and services, bridging between a “credibility-first” paradigm (exemplified by top-down information provision from systematic downscaling or impact projections) and a “salience-first” paradigm (exemplified by user-led tailored information products or storylines) by looking to identify their respective strengths and use cases. We emphasise that a more nuanced collective understanding of the dimensions of information quality in climate information and services would be beneficial to users and providers and ultimately support more confident and effective climate adaptation decisions and policy-making.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Lateglacial Interstadial to mid-Holocene stratigraphy and palynology at Pepper Arden Bottoms, North Yorkshire, UK - James B. Innes; Mairead M. Rutherford; David R. Bridgland; Ben R. Gearey; Malcolm C. Lillie; Wishart A. Mitchell; Charlotte E. O'Brien; Richard T. Jones; Gareth J. Thompson (Proceedings of the Geologists' Association, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

CYP2E1 in 1,4-dioxane metabolism and liver toxicity: insights from CYP2E1 knockout mice study - Yewei Wang; Georgia Charkoftaki; David J. Orlicky; Emily Davidson; Reza Aalizadeh; Ning Sun; Gary Ginsberg; David C. Thompson; Vasilis Vasiliou; Ying Chen (Archives of Toxicology, 2024)

Navigating ethical challenges in online wildlife trade research - Thais Q. Morcatty; Shan Su; Penthai Siriwat; Astrid Alex Andersson; Sadek Atoussi; Kim Feddema; Sergio Henriques; Jordi Janssen; Anushri Karve; Jennifer Pytka; Ruth M. Thompson; Vincent Nijman; et al. (Conservation Biology, 2024)
The surge in internet accessibility has transformed wildlife trade by facilitating the acquisition of wildlife through online platforms. This scenario presents unique ethical challenges for researchers, as traditional ethical frameworks for in‐person research cannot be readily applied to the online realm. Currently, there is a lack of clearly defined guidelines for appropriate ethical procedures when conducting online wildlife trade (OWT) research. In response to this, we consulted the scientific literature on ethical considerations in online research and examined existing guidelines established by professional societies and ethical boards. Based on these documents, we present a set of recommendations that can inform the development of ethically responsible OWT research. Key ethical challenges in designing and executing OWT research include the violation of privacy rights, defining subjects and illegality, and the risk of misinterpretation or posing risks to participants when sharing data. Potential solutions include considering participants’ expectations of privacy, defining when participants are authors versus subjects, understanding the legal and cultural context, minimizing data collection, ensuring anonymization, and removing metadata. Best practices also involve being culturally sensitive when analyzing and reporting findings. Adhering to these guidelines can help mitigate potential pitfalls and provides valuable insights to editors, researchers, and ethical review boards, enabling them to conduct scientifically rigorous and ethically responsible OWT research to advance this growing field.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

Insect meal in aquafeeds: A sustainable path to enhanced mucosal immunity in fish - S.M. Majharul Islam; Muhammad A.B. Siddik; Mette Sørensen; Monica F. Brinchmann; Kim D. Thompson; David S. Francis; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Comparison of time-domain and frequency-domain models for vibration prediction of a rail transit viaduct paved with floating slab track - Qingyuan Song; Qi Li; David J. Thompson (Engineering Structures, 2024)

Improved resilience and proteostasis mediate longevity upon DAF-2 degradation in old age - Adrian Molière; Ji Young Cecilia Park; Anita Goyala; Elena M. Vayndorf; Bruce Zhang; Kuei Ching Hsiung; Yoonji Jung; Sujeong Kwon; Cyril Statzer; David Meyer; Richard Nguyen; Joseph Chadwick; et al. (GeroScience, 2024)
Little is known about the possibility of reversing age-related biological changes when they have already occurred. To explore this, we have characterized the effects of reducing insulin/IGF-1 signaling (IIS) during old age. Reduction of IIS throughout life slows age-related decline in diverse species, most strikingly in the nematode Caenorhabditis elegans . Here we show that even at advanced ages, auxin-induced degradation of DAF-2 in single tissues, including neurons and the intestine, is still able to markedly increase C. elegans lifespan. We describe how reversibility varies among senescent changes. While senescent pathologies that develop in mid-life were not reversed, there was a rejuvenation of the proteostasis network, manifesting as a restoration of the capacity to eliminate otherwise intractable protein aggregates that accumulate with age. Moreover, resistance to several stressors was restored. These results support several new conclusions. (1) Loss of resilience is not solely a consequence of pathologies that develop in earlier life. (2) Restoration of proteostasis and resilience by inhibiting IIS is a plausible cause of the increase in lifespan. And (3), most interestingly, some aspects of the age-related transition from resilience to frailty can be reversed to a certain extent. This raises the possibility that the effect of IIS and related pathways on resilience and frailty during aging in higher animals might possess some degree of reversibility.

Characterization of macadamia ringspot-associated virus, a novel Orthotospovirus associated with Macadamia integrifolia in South Africa - Ronel Roberts; Nicola Robbertse; Genevieve D. Thompson; David A. Read (European Journal of Plant Pathology, 2024)
South Africa is the largest producer of macadamias in the world, producing an estimated 61,288 tons nut-in-shell in 2022. In order to ensure the sustainability of the industry, it is important that research focuses on the control and eradication of economically important pests and diseases. Macadamia trees in the Mpumalanga Lowveld of South Africa have for some time shown severe chlorosis, which coincides with a significant drop in production, with losses of up to 60% being recorded. The disease has since been coined Macadamia Chlorosis Disease (MCD). In an attempt to determine whether MCD may be associated with a virus, high-throughput Illumina sequencing was performed on RNA extracted from both diseased and healthy trees collected from farms in Mpumalanga. Subsequent data analyses could not link a specific virus to MCD, however, reads spanning the full genome of a novel virus belonging to the Orthotospovirus genus were obtained. An RT-PCR assay was optimized for the detection of this virus and subsequent surveys linked the virus to ringspot symptoms which are commonly observed on different macadamia cultivars. The virus has to date been identified from orchards in Mpumalanga, Limpopo and KwaZulu-Natal. Other viruses described in the genus are known to cause severe crop losses and it is therefore important that the virus, provisionally named macadamia ringspot-associated virus (MRSV), be further studied to determine whether association with this virus can lead to yield losses, and whether appropriate control strategies must be implemented to prevent the spread of MRSV.

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Imaging spectroscopy investigations in wet carbon ecosystems: A review of the literature from 1995 to 2022 and future directions - Thomas C. Ingalls; Jiwei Li; Yvonne Sawall; Roberta E. Martin; David R. Thompson; Gregory P. Asner (Remote Sensing of Environment, 2024)

An individual-based model for direct and indirect transmission of chronic wasting disease in free-ranging white-tailed deer - Noelle E Thompson; David J Butts; Michael S Murillo; Daniel J O'Brien; Sonja A Christensen; William F Porter; Gary J Roloff (Ecological Modelling, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Genotype-by-environment interactions and local adaptation shape selection in the US National Chip Processing Trial - Husain I. Agha; Jeffrey B. Endelman; Jessica Chitwood-Brown; Mark Clough; Joseph Coombs; Walter S. De Jong; David S. Douches; Charles R. Higgins; David G. Holm; Richard Novy; Marcio F. R. Resende; Vidyasagar Sathuvalli; et al. (Theoretical and Applied Genetics, 2024)
Key message We find evidence of selection for local adaptation and extensive genotype-by-environment interaction in the potato National Chip Processing Trial (NCPT). Abstract We present a novel method for dissecting the interplay between selection, local adaptation and environmental response in plant breeding schemes. Balancing local adaptation and the desire for widely adapted cultivars is challenging for plant breeders and makes genotype-by-environment interactions (GxE) an important target of selection. Selecting for GxE requires plant breeders to evaluate plants across multiple environments. One way breeders have accomplished this is to test advanced materials across many locations. Public potato breeders test advanced breeding material in the National Chip Processing Trial (NCPT), a public–private partnership where breeders from ten institutions submit advanced chip lines to be evaluated in up to ten locations across the country. These clones are genotyped and phenotyped for important agronomic traits. We used these data to interrogate the NCPT for GxE. Further, because breeders submitting clones to the NCPT select in a relatively small geographic range for the first 3 years of selection, we examined these data for evidence of incidental selection for local adaptation, and the alleles underlying it, using an environmental genome-wide association study (envGWAS). We found genomic regions associated with continuous environmental variables and discrete breeding programs, as well as regions of the genome potentially underlying GxE for yield.

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Life goes on: Spatial heterogeneity promotes biodiversity in an urbanized coastal marine ecosystem - Shelby E. McIlroy; Isis Guibert; Anand Archana; Wing Yi Haze Chung; J. Emmett Duffy; Rinaldi Gotama; Jerome Hui; Nancy Knowlton; Matthieu Leray; Chris Meyer; Gianni Panagiotou; Gustav Paulay; et al. (Global Change Biology, 2024)
Both human populations and marine biodiversity are concentrated along coastlines, with growing conservation interest in how these ecosystems can survive intense anthropogenic impacts. Tropical urban centres provide valuable research opportunities because these megacities are often adjacent to mega‐diverse coral reef systems. The Pearl River Delta is a prime exemplar, as it encompasses one of the most densely populated and impacted regions in the world and is located just northwest of the Coral Triangle. However, the spatial and taxonomic complexity of this biodiversity, most of which is small, cryptic in habitat and poorly known, make comparative analyses challenging. We deployed standardized settlement structures at seven sites differing in the intensity of human impacts and used COI metabarcoding to characterize benthic biodiversity, with a focus on metazoans. We found a total of 7184 OTUs, with an average of 665 OTUs per sampling unit; these numbers exceed those observed in many previous studies using comparable methods, despite the location of our study in an urbanized environment. Beta diversity was also high, with 52% of the OTUs found at just one site. As expected, we found that the sites close to point sources of pollution had substantially lower diversity (44% less) relative to sites bathed in less polluted oceanic waters. However, the polluted sites contributed substantially to the total animal diversity of the region, with 25% of all OTUs occurring only within polluted sites. Further analysis of Arthropoda, Annelida and Mollusca showed that phylogenetic clustering within a site was common, suggesting that environmental filtering reduced biodiversity to a subset of lineages present within the region, a pattern that was most pronounced in polluted sites and for the Arthropoda. The water quality gradients surrounding the PRD highlight the unique role of in situ studies for understanding the impacts of complex urbanization pressures on biodiversity.

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

Measures of Subjective Memory for People with Epilepsy: A Systematic Review of Measurement Properties - Kate Thompson; Ada H. Y. Lo; Hannah L. McGlashan; Tamara Ownsworth; Catherine Haslam; Alan Pegna; David C. Reutens (Neuropsychology Review, 2024)

Scaling of fast‐start performance and its thermal dependence in mummichog Fundulus heteroclitus - David C. Collar; Trevor J. Hobbs; Jessica S. Thompson (Journal of Fish Biology, 2024)
Fast‐start predator‐escape performance and its sensitivity to temperature (24, 30, and 36°C) were evaluated in mummichog Fundulus heteroclitus across a range of body sizes spanning YOY to adult (35–68 mm standard length). Mummichogs exhibit isometry of body dimensions and areas of the dorsal and anal fins but negative allometry of the caudal fin area. These scaling relationships are consistent with observed decreases in fast‐start angular velocities with increasing body size. Linear velocity, on the contrary, does not vary with size, and both large and small mummichogs are capable of traversing similar distances in a given amount of time. In addition, temperature influences fast‐start performance in similar ways over the size range, though the magnitude of the effect varies with size for some performance measures. In general, fast‐start performance increases with test temperature, but mummichogs acclimated to warmer temperatures exhibit lower performance at each test temperature. Altogether, our results suggest that mummichogs across the adult size range may suffer decreases in their predator‐escape performance as increasing sea temperatures combine with short‐term temperature fluctuations in the estuaries these fish occupy.

A hyperspectral view of the nearshore Mississippi River Delta: Characterizing suspended particles in coastal wetlands using imaging spectroscopy - Joshua P. Harringmeyer; Nilotpal Ghosh; Matthew W. Weiser; David R. Thompson; Marc Simard; Steven E. Lohrenz; Cédric G. Fichot (Remote Sensing of Environment, 2024)

Polycyclic aromatic hydrocarbons in tropical Australian stalagmites: a framework for reconstructing paleofire activity - Elena Argiriadis; Rhawn F. Denniston; Stefania Ondei; David M.J.S. Bowman; Giulia Genuzio; Huong Quynh Anh Nguyen; Jamie Thompson; Mattia Baltieri; Jonathan Azenon; John Cugley; David Woods; William F. Humphreys; et al. (Geochimica et Cosmochimica Acta, 2024)

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Spatially constrained atmosphere and surface retrieval for imaging spectroscopy - Regina Eckert; Steffen Mauceri; David R. Thompson; Jay E. Fahlen; Philip G. Brodrick (Remote Sensing of Environment, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Simultaneous stream assessment of antibiotics, bacteria, antibiotic resistant bacteria, and antibiotic resistance genes in an agricultural region of the United States - Carrie E. Givens; Dana W. Kolpin; Laura E. Hubbard; Shannon M. Meppelink; David M. Cwiertny; Darrin A. Thompson; Rachael F. Lane; Michaelah C. Wilson (Science of The Total Environment, 2023)

Sustainable bioleaching of lithium-ion batteries for critical metal recovery: Process optimization through design of experiments and thermodynamic modeling - Majid Alipanah; Hongyue Jin; Qiang Zhou; Caitlin Barboza; David Gazzo; Vicki Thompson; Yoshiko Fujita; Jiangping Liu; Andre Anderko; David Reed (Resources, Conservation and Recycling, 2023)

TEA of the CO2 capture process in pre-combustion applications using thirty-five physical solvents: Predictions with ANN - Husain E. Ashkanani; Rui Wang; Wei Shi; Nicholas S. Siefert; Robert L. Thompson; Kathryn H. Smith; Janice A. Steckel; Isaac K. Gamwo; David Hopkinson; Kevin Resnik; Badie I. Morsi (International Journal of Greenhouse Gas Control, 2023)

Magnesium oxide loaded mesoporous silica: Synthesis, characterisation and use in removing lead and cadmium from water supplies - Wahran M. Saod; Ian W. Oliver; David F. Thompson; Simon Holborn; Alessandro Contini; Vladimir Zholobenko (Environmental Nanotechnology, Monitoring & Management, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Multi-omics profiling reveals cellular pathways and functions regulated by ALDH1B1 in colon cancer cells - Yewei Wang; Zeljka Popovic; Georgia Charkoftaki; Rolando Garcia-Milian; TuKiet T. Lam; David C. Thompson; Ying Chen; Vasilis Vasiliou (Chemico-Biological Interactions, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The effect of general practice contact on cancer stage at diagnosis in Aboriginal and non-Aboriginal residents of New South Wales - David Banham; David Roder; Sandra Thompson; Anna Williamson; Freddie Bray; David Currow (Cancer Causes & Control, 2023)
Purpose Older age, risks from pre-existing health conditions and socio-economic disadvantage are negatively related to the prospects of an early-stage cancer diagnosis. With older Aboriginal Australians having an elevated prevalence of these underlying factors, this study examines the potential for the mitigating effects of more frequent contact with general practitioners (GPs) in ensuring local-stage at diagnosis. Methods We compared the odds of local vs. more advanced stage at diagnosis of solid tumours according to GP contact, using linked registry and administrative data. Results were compared between Aboriginal ( n = 4,084) and non-Aboriginal ( n = 249,037) people aged 50 + years in New South Wales with a first diagnosis of cancer in 2003–2016. Results Younger age, male sex, having less area-based socio-economic disadvantage, and fewer comorbid conditions in the 12 months before diagnosis (0–2 vs. 3 +), were associated with local-stage in fully-adjusted structural models. The odds of local-stage with more frequent GP contact (14 + contacts per annum) also differed by Aboriginal status, with a higher adjusted odds ratio (aOR) of local-stage for frequent GP contact among Aboriginal people (aOR = 1.29; 95% CI 1.11–1.49) but not among non-Aboriginal people (aOR = 0.97; 95% CI 0.95–0.99). Conclusion Older Aboriginal Australians diagnosed with cancer experience more comorbid conditions and more socioeconomic disadvantage than other Australians, which are negatively related to diagnosis at a local-cancer stage. More frequent GP contact may act to partly offset this among the Aboriginal population of NSW.

Horse fly and deer fly (Diptera: Tabanidae) species and abundance following logging in northwestern Ontario - Janette Buckley; James A. Schaefer; John L. Ringrose; Marco Raponi; Ian D. Thompson; Philip A. Wiebe; Art R. Rodgers; John M. Fryxell; David V. Beresford (Forest Ecology and Management, 2023)

Adaptation and mitigation capacity of wildland forests in the northeastern United States - Edward K. Faison; Danelle Laflower; Luca L. Morreale; David R. Foster; Brian Hall; Emily Johnson; Jonathan R. Thompson (Forest Ecology and Management, 2023)

Effect of pelleting on the enzymatic digestibility of corn stover - Xueli Chen; Antonio C. Freitas dos Santos; Diana M. Ramirez Gutierrez; Peiyuan Song; John E. Aston; David N. Thompson; James H. Dooley; Michael R. Ladisch; Nathan S. Mosier (Bioresource Technology, 2023)

Tilapia lake virus disease: Vaccine strategies to control the threat to tilapia aquaculture - Sreeja Lakshmi; David Smith; Ha Thanh Dong; Kim D. Thompson; Preetham Elumalai (Reviews in Aquaculture, 2023)
Since the first report of a novel disease caused by tilapia lake virus (TiLV) in 2014, the disease (TiLVD) has gained considerable attention as one of the most devastating viral diseases in tilapia aquaculture globally. The virus is both highly virulent and transmissible and has been detected in many countries worldwide. It poses a severe threat to the global tilapia aquaculture industry, food security and many people's livelihoods in low and middle‐income countries. The absence of effective treatment strategies and inadequate biosecurity measures means the virus's rapid spread is likely to continue. Vaccination has proven to be an effective approach to preventing and controlling disease in finfish aquaculture. The vaccine's efficacy and the delivery system's suitability are essential for evoking an appropriate immune response against the pathogen. The purpose of this review is to provide an overview of the strategies being used to develop vaccines for TiLVD. Nanovaccines, which offer a new approach to prevent TiLVD in farmed tilapia, are also discussed.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Modeling the effects of interior headland restoration on estuarine sediment transport processes in a marine-dominant estuary - Robert L. Jenkins; Davina L. Passeri; Christopher G. Smith; David M. Thompson; Kathryn E. L. Smith (Frontiers in Marine Science, 2023)
The effects of interior headland restoration on estuarine sediment transport processes were assessed through process-based numerical modeling. Three proposed interior headland restoration scenarios in the Grand Bay estuary (Mississippi/Alabama) were modeled using Delft3D to understand impacts on suspended sediment concentrations, bed level morphology, and sediment fluxes under present-day conditions and a sea level rise (SLR) of 0.5 m, representing a high projection of SLR by the year 2050. Model results showed localized differences in bed levels near the restored features after a year of simulated morphologic change. The restored headland features acted as a sediment source to the immediate surroundings while also providing some non-significant sheltering effect of backshore shoals and marsh shorelines. Sediment fluxes were sensitive to wind directions and the presence of the restored headlands. However, regardless of wind direction, mean sea level, or restoration action, the greatest sediment fluxes were always export fluxes from the estuary, which were further increased with increased sea level. Suspended sediment concentrations were highly influenced by SLR in a non-linear manner. Sediment concentrations both increased and decreased depending on depth under SLR. Furthermore, SLR allowed for the suspension and deposition of sediments on the marsh platform. Overall, the influence of SLR was more impactful to changing sediment dynamics than the influence of the restoration features.

Identifying the drivers of silky shark distribution and an evaluation of protection measures - Shona Murray; Jessica J. Meeuwig; Christopher D. H. Thompson; David Mouillot (Environmental Biology of Fishes, 2023)
The silky shark ( Carcharhinus falciformi s) has experienced a significant population decline associated with intense targeted and incidental fishing pressure. Large marine protected areas (MPAs) are increasingly advocated for the conservation of oceanic species like silky sharks, recognising that the benefits of MPAs to such species depend on a comprehensive understanding of their distribution, abundance and life history. We combined mid-water stereo-baited remote underwater video system (BRUVS) records with environmental, geographic and anthropogenic variables to document the distribution and abundance of silky shark populations, identify the most important predictors of their presence, abundance and body size, and determine if their abundance is greater within MPAs than in locations not designated as MPAs. From 1418 deployments of mid-water BRUVS across three ocean basins, 945 silky sharks were identified at 18 locations, with young-of-year ( < 87 cm TL) observed at four of these. Our study revealed generally low abundances of silky sharks as recorded on mid-water BRUVS across their cosmopolitan distribution, although our models identified seamounts as hotspots of abundance. Human pressure was a significant variable within our models, with proximity to human populations and ports being key drivers of silky shark abundance and body size. We did not observe a higher abundance of silky sharks inside MPAs compared to locations not designated as MPAs, suggesting that these MPAs have not been placed in areas where silky sharks remain relatively abundant. We therefore recommend expanding the current MPA network in line with the 30 × 30 initiative to more effectively protect key habitats such as seamounts.

Advances in Design and Development of Lumi-Solve: A Novel Drug-Eluting Photo-Angioplasty Device - Amarnath Sangeetha Menon; Igor Subasic de Azevedo; Kylie Choong; Dhruv Bhatnagar; Chen Wang; Pavel Sluka; David R. Chisholm; Paul Pasic; Helmut Thissen; Gopal Sama; Andrea Robinson; Andrew Rodda; et al. (Cardiovascular Engineering and Technology, 2023)
Purpose The Lumi-Solve photo-angioplasty drug eluting balloon catheter (DEBc) may afford safety advantages over current DEBc. Lumi-Solve utilises the guidewire (GW) port and lumen to deliver fibre-optic UV365nm light to the angioplasty balloon which may be problematic. We explore and evaluate alternative Lumi-Solve design options to circumvent fibre-optic use of the GW port and lumen which may enhance efficacy and clinical utility. Methods Effects of guidewire shadowing (GWS) on visible and UV365nm light transmission were evaluated and modelled in-silico. To evaluate the effect of a dedicated intra-balloon fibre-optic port, modified angioplasty balloons and sections of translucent polyethylene terephthalate (PET) GW port tubing were utilised. Investigation of the effect of GWS on chemical and biological photo-activation of balloon surface drug was performed utilising LCMS analysis and inhibition of histone deacetylase activity (HDACi) was measured in human umbilical vein endothelial cells (HUVEC). Results Parallel fibre-optic and GW port configurations generated a GWS of approximately 18.0% of the evaluable balloon surface area and attenuated both visible and UV light intensity by 20.0–25.0% and reduced chemical photo-activation of balloon surface drug and HDACi by at least 40–45%. Alternative fibre-optic port configurations including a spiral design significantly mitigated GWS effects on UV light transmission. Conclusions To avoid use of the GW port and its associated complications a dedicated third port and lumen for the Lumi-Solve fibre-optic may be required. To maximize balloon surface chemical and biological photo-activation, non-parallel, intra-balloon, fibre-optic lumen trajectories, including a spiral design may be useful.

The distribution of coastal fish eDNA sequences in the Anthropocene - Laetitia Mathon; Virginie Marques; Stéphanie Manel; Camille Albouy; Marco Andrello; Emilie Boulanger; Julie Deter; Régis Hocdé; Fabien Leprieur; Tom B. Letessier; Nicolas Loiseau; Eva Maire; et al. (Global Ecology and Biogeography, 2023)
Aim Coastal fishes have a fundamental role in marine ecosystem functioning and contributions to people, but face increasing threats due to climate change, habitat degradation and overexploitation. The extent to which human pressures are impacting coastal fish biodiversity in comparison with geographic and environmental factors at large spatial scale is still under scrutiny. Here, we took advantage of environmental DNA (eDNA) metabarcoding to investigate the relationship between fish biodiversity, including taxonomic and genetic components, and environmental but also socio‐economic factors. Location Tropical, temperate and polar coastal areas. Time period Present day. Major taxa studied Marine fishes. Methods We analysed fish eDNA in 263 stations (samples) in 68 sites distributed across polar, temperate and tropical regions. We modelled the effect of environmental, geographic and socio‐economic factors on α‐ and β‐diversity. We then computed the partial effect of each factor on several fish biodiversity components using taxonomic molecular units (MOTU) and genetic sequences. We also investigated the relationship between fish genetic α‐ and β‐diversity measured from our barcodes, and phylogenetic but also functional diversity. Results We show that fish eDNA MOTU and sequence α‐ and β‐diversity have the strongest correlation with environmental factors on coastal ecosystems worldwide. However, our models also reveal a negative correlation between biodiversity and human dependence on marine ecosystems. In areas with high dependence, diversity of all fish, cryptobenthic fish and large fish MOTUs declined steeply. Finally, we show that a sequence diversity index, accounting for genetic distance between pairs of MOTUs, within and between communities, is a reliable proxy of phylogenetic and functional diversity. Main conclusions Together, our results demonstrate that short eDNA sequences can be used to assess climate and direct human impacts on marine biodiversity at large scale in the Anthropocene and can further be extended to investigate biodiversity in its phylogenetic and functional dimensions.

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Use of equine embryo-derived mesenchymal stromal cells and their extracellular vesicles as a treatment for persistent breeding-induced endometritis in susceptible mares - Fiona K Hollinshead; David W Hanlon; Weilin Hou; Zoe Tasma; Tanvi Damani; Riley E Thompson; Mindy A Meyers; Christianne Magee; Dilyara A Murtazina; Colin M Clay; Larry W Chamley (Journal of Equine Veterinary Science, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

A positive temperature‐dependent effect of elevated CO 2 on growth and lipid accumulation in the planktonic copepod, Calanus finmarchicus - David M. Fields; Jeffrey A. Runge; Cameron R. S. Thompson; Caroline M. F. Durif; Steven D. Shema; Reidun M. Bjelland; Maura Niemisto; Michael T. Arts; Anne Berit Skiftesvik; Howard I. Browman (Limnology and Oceanography, 2023)
Calanus finmarchicus were reared from eggs to adults at 12°C and 16°C with non‐limiting food in combination with ambient (600 μ atm) and high (1100 μ atm) p CO 2 . These conditions are likely to be encountered by the species at the southern margins of its biogeographical range by the end of the century. Dry weight (DW), carbon (C) and nitrogen (N) mass, oil‐sac volume (OSV), fatty acid composition (FA), and oxygen consumption rates (OCR) were measured on newly molted stage CV copepodites and recently molted adult females. By focusing our measurements on these precise events in the life cycle, we were able to obtain a more accurate comparison of growth and respiration across treatments. Copepods raised at 12°C had a significantly greater DW, OSV, and C and N mass than those raised at 16°C High p CO 2 , independent of temperature, was associated with a further increase in the DW and C content of the copepods. Interactive effects of temperature and p CO 2 resulted in a larger OSV at low temperature and high p CO 2 . Mass‐specific respiration rates were significantly lower at lower temperatures and elevated p CO 2 suggesting that the increase in mass (DW, C, and OSV) resulted from reduced metabolic cost. The composition of fatty acids in the copepods varied mainly with temperature. Two fatty acids varied with p CO 2 : 16:0 tended to decrease with higher p CO 2 and 18:3n−3 tended to increase with higher p CO 2 . These observations suggest that elevated p CO 2 /lower pH in future oceans may have a beneficial effect on C. finmarchicus .

Climate warming has direct and indirect effects on microbes associated with carbon cycling in northern lakes - Johanna C. Winder; Lucas P. P. Braga; McKenzie A. Kuhn; Lauren M. Thompson; David Olefeldt; Andrew J. Tanentzap (Global Change Biology, 2023)
Northern lakes disproportionately influence the global carbon cycle, and may do so more in the future depending on how their microbial communities respond to climate warming. Microbial communities can change because of the direct effects of climate warming on their metabolism and the indirect effects of climate warming on groundwater connectivity from thawing of surrounding permafrost, especially at lower landscape positions. Here we used shotgun metagenomics to compare the taxonomic and functional gene composition of sediment microbes in 19 peatland lakes across a 1600‐km permafrost transect in boreal western Canada. We found microbes responded differently to the loss of regional permafrost cover than to increases in local groundwater connectivity. These results suggest that both the direct and indirect effects of climate warming, which were respectively associated with loss of permafrost and subsequent changes in groundwater connectivity interact to change microbial composition and function. Archaeal methanogens and genes involved in all major methanogenesis pathways were more abundant in warmer regions with less permafrost, but higher groundwater connectivity partly offset these effects. Bacterial community composition and methanotrophy genes did not vary with regional permafrost cover, and the latter changed similarly to methanogenesis with groundwater connectivity. Finally, we found an increase in sugar utilization genes in regions with less permafrost, which may further fuel methanogenesis. These results provide the microbial mechanism for observed increases in methane emissions associated with loss of permafrost cover in this region and suggest that future emissions will primarily be controlled by archaeal methanogens over methanotrophic bacteria as northern lakes warm. Our study more generally suggests that future predictions of aquatic carbon cycling will be improved by considering how climate warming exerts both direct effects associated with regional‐scale permafrost thaw and indirect effects associated with local hydrology.

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Shape from spectra - Nimrod Carmon; Alexander Berk; Niklas Bohn; Phillip G. Brodrick; Jeff Dozier; Margaret Johnson; Charles E. Miller; David R. Thompson; Michael Turmon; Charles M. Bachmann; Robert O. Green; Regina Eckert; et al. (Remote Sensing of Environment, 2023)

A Qualitative Study of Factors Influencing Food Choices and Food Sources Among Adults Aged 50 Years and Older During the Coronavirus Disease 2019 Pandemic - Patrick J. Brady; Natoshia M. Askelson; Helaina Thompson; Sarah Kersten; Haley Hopkins; Sato Ashida; Faryle Nothwehr; Brandi Janssen; David Frisvold (Journal of the Academy of Nutrition and Dietetics, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Wildfire Response: A System on the Brink? - Matthew P Thompson; Erin J Belval; Jude Bayham; David E Calkin; Crystal S Stonesifer; David Flores (Journal of Forestry, 2023)
Increasing wildfire activity, decreasing workforce capacity, and growing systemic strain may result in an interagency wildfire-response system less capable of protecting landscapes and communities. Further, increased workloads will likely increase hazards to fire personnel and amplify existing problems with recruitment and retention. In the face of elevated risks and degraded capacity, it is imperative that the wildfire-response system operate efficiently. Viable solutions are urgently needed that enable the system to do more with less and that manage not only for landscapes and communities but also the health and wellbeing of the fire personnel on whom the system relies. Achieving this will likely require rethinking how the interagency wildfire-response system can more adaptively and intelligently deploy fire personnel by leveraging enhanced logistics, operations, and proven fire analytics.

The role of field-collected cues in the host recognition of twig girdlers (Oncideres rhodosticta) on honey mesquite (Prosopis glandulosa) - Ikju Park; David C. Thompson (Journal of Asia-Pacific Entomology, 2023)

Performance of hydrophobic physical solvents for pre-combustion CO2 capture at a pilot scale coal gasification facility - Kathryn H. Smith; Husain E. Ashkanani; Robert L. Thompson; Jeffrey T. Culp; Lei Hong; Mike Swanson; Joshua Stanislowski; Wei Shi; Badie I. Morsi; Kevin Resnik; David P. Hopkinson; Nicholas S. Siefert (International Journal of Greenhouse Gas Control, 2023)

Evaluating the performance of conservation translocations in large carnivores across the world - Seth Thomas; Vincent van der Merwe; William Douglas Carvalho; Cristina Harumi Adania; Rok Černe; Tomislav Gomerčić; Miha Krofel; Jeffrey Thompson; Roy T. McBride; Jose Hernandez-Blanco; Anna Yachmennikova; David W. Macdonald; et al. (Biological Conservation, 2023)

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Controls on methylmercury concentrations in lakes and streams of peatland‐rich catchments along a 1700 km permafrost gradient - Lauren M. Thompson; McKenzie A. Kuhn; Johanna C. Winder; Lucas P. P. Braga; Ryan H. S. Hutchins; Andrew J. Tanentzap; Vincent L. St. Louis; David Olefeldt (Limnology and Oceanography, 2023)
Permafrost thaw may increase the production of neurotoxic methylmercury (MeHg) in northern peatlands, but the downstream delivery of MeHg is uncertain. We quantified total mercury (THg) and MeHg concentrations in lakes and streams along a 1700 km permafrost transect in boreal western Canada to determine the influence of regional permafrost extent compared to local lake and catchment characteristics. In lakes, we assessed sediment microbial communities and modeled potential rates of water column photodemethylation (PD). Regardless of permafrost conditions, peatlands were the primary sources of MeHg across the transect as MeHg concentrations in streams increased with aromatic dissolved organic carbon (DOC), iron, and lower pH. Higher DOC and greater catchment peatland extent were further associated with higher stream %MeHg (MeHg/THg). Peatland lakes were potential MeHg sinks, with lower MeHg concentrations than streams (mean ± 1SD: 0.19 ± 0.23 and 0.47 ± 0.77 ng MeHg L −1 , respectively), and larger stream catchments had lower %MeHg where PD may occur in abundant small lakes. Microbial communities in lake sediments showed that abundance of Hg reducing genes ( mer A) predominated over Hg methylating ( hgc A) and MeHg demethylating ( mer B) genes. The effects of permafrost extent on MeHg processes in lakes were secondary to the influence of local catchment characteristics, but lakes in regions with less permafrost had higher DOC concentrations, higher %MeHg, and lower potential rates of PD. Our study highlights a need to understand the impacts of climate change on MeHg source and sink processes, particularly as mediated through changes to peatland DOC, to improve projections of future MeHg concentrations in northern catchments.

Urgent assessment needed to evaluate potential impacts on cetaceans from deep seabed mining - Kirsten F. Thompson; Kathryn A. Miller; Jake Wacker; Solène Derville; Christopher Laing; David Santillo; Paul Johnston (Frontiers in Marine Science, 2023)
Deep seabed mining operations, if permitted, could present significant risks to ocean ecosystems. Disturbance on any scale is likely to be long lasting and irreversible. Scant research to date has examined the impact that deep sea minerals extraction would have on cetaceans. The Clarion-Clipperton Zone (CCZ) is of particular interest to mining companies aiming to exploit polymetallic nodules. The CCZ, with an average depth of 5,500 m and an area of approximately 11,650,000 km 2 , is a habitat for cetaceans including baleen (mysticetes) and toothed whales (odontocetes). Of particular concern is anthropogenic noise. If permitted, commercial-scale mining is expected to operate 24-hours a day, at varying depths. The sounds produced from mining operations, including from remotely operated vehicles on the seafloor, overlap with the frequencies at which cetaceans communicate, which can cause auditory masking and behavior change in marine mammals. Cetaceans are already facing numerous stressors, including climate change, and many species are still recovering from centuries of exploitation. We argue the need for urgent research to assess more fully the potential impact of deep seabed mining on cetaceans.

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

Getting the most out of maths: How to coordinate mathematical modelling research to support a pandemic, lessons learnt from three initiatives that were part of the COVID-19 response in the UK - Ciara E. Dangerfield; I. David Abrahams; Chris Budd; Matt Butchers; Michael E. Cates; Alan R. Champneys; Christine S.M. Currie; Jessica Enright; Julia R. Gog; Alain Goriely; T. Déirdre Hollingsworth; Rebecca B. Hoyle; et al. (Journal of Theoretical Biology, 2023)

Sustainable bioleaching of lithium-ion batteries for critical materials recovery - Majid Alipanah; David Reed; Vicki Thompson; Yoshiko Fujita; Hongyue Jin (Journal of Cleaner Production, 2023)

Genomic and phylogenetic characterization of wheat yellows virus, a novel tenuivirus infecting wheat in South Africa - David A. Read; Ronel Roberts; Goddy Prinsloo; Genevieve D. Thompson (Archives of Virology, 2023)

Steelhead trout (Oncorhynchus mykiss) fed probiotic during the earliest developmental stages have enhanced growth rates and intestinal microbiome bacterial diversity - Ian S. Hines; Kevin D. Santiago-Morales; Clay S. Ferguson; Jireh Clarington; Meaghan Thompson; Meghann Rauschenbach; Uri Levine; David Drahos; Frank O. Aylward; Stephen A. Smith; David D. Kuhn; Ann M. Stevens (Frontiers in Marine Science, 2022)
Sustainable aquaculture practices can help meet the increasing human demand for seafood, while easing pressures on natural fish populations. Studies aimed at increasing fish production in aquaculture have included supplementary dietary probiotics that often promote general health and enhanced growth rates by altering the microbiome of the host. Steelhead trout ( Oncorhynchus mykiss ) is anadromous, like salmon, and it is a subspecies of rainbow trout capable of rapid growth, making it an attractive fish to the aquaculture industry. In this study, the impact of feeding a Bacillus subtilis probiotic on the bacterial microbiome of steelhead trout was examined temporally across several stages of animal development, from eggs (day -19) through 184 days after hatching, in relation to physiological measures. Diets included: commercial feed only as a control (A), continually-fed probiotic top-coated on commercial feed (B), commercial then switch to probiotic feed (C), or probiotic then switch to commercial feed (D). Validation of probiotic concentrations on feed and in fish tissues was performed using CFU/g and qPCR, respectively. Fish growth was measured and samples for intestinal microbiome analyses were collected at multiple timepoints during fish development. Fish fed diet D yielded higher weights than the other three diets, with little impact on other biometric parameters. However, bacterial microbiome analysis indicated an increasing trend of overall alpha diversity from the egg stage to day 29 for fish fed the various diets with diet D having the highest diversity. Fish fed diets A and D maintained a high alpha diversity beyond day 29 in contrast to a decreased trend for fish still being fed probiotics in diets B and C. The fish fed diets B and C harbored a significantly higher relative abundance of Bacillus sp. in their total microbiomes (feces + mucosa). Interestingly, the mucosal-only microbiome indicated little variation between the four groups of fish. Feeding the probiotic earlier in development, during the hatchery phase, to influence bacterial microbiome composition in the intestine (rather than later after the microbiome has been established) appears to be a more effective aquaculture practice by enhancing microbiome diversity while enabling higher fish yields.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management - Matt I. D. Carter; Lars Boehme; Michelle A. Cronin; Callan D. Duck; W. James Grecian; Gordon D. Hastie; Mark Jessopp; Jason Matthiopoulos; Bernie J. McConnell; David L. Miller; Chris D. Morris; Simon E. W. Moss; et al. (Frontiers in Marine Science, 2022)
Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by spatial coverage of animal-borne tracking data. Grey ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) are sympatric predators in North Atlantic shelf seas. The United Kingdom (UK) and Ireland represents an important population centre for both species, and Special Areas of Conservation (SACs) are designated for their monitoring and protection. Here we use an extensive high-resolution GPS tracking dataset, unprecedented in both size (114 grey and 239 harbour seals) and spatial coverage, to model habitat preference and generate at-sea distribution estimates for the entire UK and Ireland populations of both species. We found regional differences in environmental drivers of distribution for both species which likely relate to regional variation in diet and population trends. Moreover, we provide SAC-specific estimates of at-sea distribution for use in marine spatial planning, demonstrating that hotspots of at-sea density in UK and Ireland-wide maps cannot always be apportioned to the nearest SAC. We show that for grey seals, colonial capital breeders, there is a mismatch between SACs (where impacts are likely to be detected) and areas where impacts are most likely to occur (at sea). We highlight an urgent need for further research to elucidate the links between at-sea distribution during the foraging season and population trends observed in SACs. More generally, we highlight that the potential for such a disconnect needs to be considered when designating and managing protected sites, particularly for species that aggregate to breed and exhibit partial migration (e.g. grey seals), or spatial variation in migration strategies. We demonstrate the use of strategic tracking efforts to predict distribution across multiple regions, but caution that such efforts should be mindful of the potential for differences in species-environment relationships despite similar accessible habitats.

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The impact of age, sex, cardio-respiratory fitness, and cardiovascular disease risk on dynamic cerebral autoregulation and baroreflex sensitivity - Joseph D. Maxwell; Daniel J. Bannell; Aine Brislane; Sophie E. Carter; Gemma D. Miller; Kirsty A. Roberts; Nicola D. Hopkins; David A. Low; Howard H. Carter; Andrew Thompson; Jurgen A. H. R. Claassen; Dick H. J. Thijssen; et al. (European Journal of Applied Physiology, 2022)
Background Humans display an age-related decline in cerebral blood flow and increase in blood pressure (BP), but changes in the underlying control mechanisms across the lifespan are less well understood. We aimed to; (1) examine the impact of age, sex, cardiovascular disease (CVD) risk, and cardio-respiratory fitness on dynamic cerebral autoregulation and cardiac baroreflex sensitivity, and (2) explore the relationships between dynamic cerebral autoregulation (dCA) and cardiac baroreflex sensitivity (cBRS). Methods 206 participants aged 18–70 years were stratified into age categories. Cerebral blood flow velocity was measured using transcranial Doppler ultrasound. Repeated squat-stand manoeuvres were performed (0.10 Hz), and transfer function analysis was used to assess dCA and cBRS. Multivariable linear regression was used to examine the influence of age, sex, CVD risk, and cardio-respiratory fitness on dCA and cBRS. Linear models determined the relationship between dCA and cBRS. Results Age, sex, CVD risk, and cardio-respiratory fitness did not impact dCA normalised gain, phase, or coherence with minimal change in all models ( P > 0.05). cBRS gain was attenuated with age when adjusted for sex and CVD risk (young–older; β = − 2.86 P < 0.001) along with cBRS phase (young–older; β = − 0.44, P < 0.001). There was no correlation between dCA normalised gain and phase with either parameter of cBRS. Conclusion Ageing was associated with a decreased cBRS, but dCA appears to remain unchanged. Additionally, our data suggest that sex, CVD risk, and cardio-respiratory fitness have little effect.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Is Neuroscience FAIR? A Call for Collaborative Standardisation of Neuroscience Data - Jean-Baptiste Poline; David N. Kennedy; Friedrich T. Sommer; Giorgio A. Ascoli; David C. Van Essen; Adam R. Ferguson; Jeffrey S. Grethe; Michael J. Hawrylycz; Paul M. Thompson; Russell A. Poldrack; Satrajit S. Ghosh; David B. Keator; et al. (Neuroinformatics, 2022)
In this perspective article, we consider the critical issue of data and other research object standardisation and, specifically, how international collaboration, and organizations such as the International Neuroinformatics Coordinating Facility (INCF) can encourage that emerging neuroscience data be Findable, Accessible, Interoperable, and Reusable (FAIR) . As neuroscientists engaged in the sharing and integration of multi-modal and multiscale data, we see the current insufficiency of standards as a major impediment in the Interoperability and Reusability of research results. We call for increased international collaborative standardisation of neuroscience data to foster integration and efficient reuse of research objects.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Hydrogen Sulfide Production with a Microbial Consortium Isolated from Marine Sediments Offshore - Roberto Briones-Gallardo; Muriel González-Muñoz; Itza García-Bautista; David Valdés-Lozano; Tanit Toledano-Thompson; Erik Polanco-Lugo; Renata Rivera-Madrid; Ruby Valdez-Ojeda (Journal of Marine Science and Engineering, 2022)
Hydrogen, electric energy production, and metal toxic bioremediation are some of the biotechnological applications of sulfate-reducing organisms, which potentially depend on the sulfide produced. In this study, offshore of Yucatan, the capacity to produce hydrogen sulfide using microbial consortia from marine sediment (SC469, PD102, SD636) in batch reactors was evaluated. Kinetic tests were characterized by lactate oxidation to acetate, propionate, CO2 and methane. The inoculum SC469, located in open-ocean, differed strongly in microbial diversity and showed better performance in substrate utilization with the highest hydrogen sulfide production (246 mmolg−1 VSS) at a specific hydrogen sulfide rate of 113 mmol g−1 VSS d−1 with a 0.79 molar ratio of sulfate/lactate. Sulfate-reducing microbial consortia enriched in the laboratory from marine sediments collected offshore in Yucatan and with a moderate eutrophication index, differed strongly in microbial diversity with loss of microorganisms with greater capacity for degradation of organic macromolecules. The sulfate-reducing microorganisms were characterized using Illumina MiSeq technology and were mainly Desulfomicrobium, Clostridium and Desulfobacter.

Genomic characterization of grapevine viruses N and O: novel vitiviruses from South Africa - David A. Read; Genevieve D. Thompson; Nathan Le Cordeur; Dirk Swanevelder; Gerhard Pietersen (Archives of Virology, 2022)

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Socio-environmental drivers of establishment of Lymantria dispar, a nonnative forest pest, in the United States - Rebecca Epanchin-Niell; Jieyi Lu; Alexandra Thompson; Patrick C. Tobin; David R. Gray; Andrew M. Liebhold (Biological Invasions, 2022)

Rapid spatial expansion and population increase of invasive lionfish (Pterois spp.) observed on natural habitats in the northern Gulf of Mexico - Matthew D. Campbell; Adam G. Pollack; Kevin Thompson; Ted Switzer; William B. Driggers; Eric R. Hoffmayer; Sean Keenan; Chris Gardner; David Hanisko; Kevin R. Rademacher; Kate Overly (Biological Invasions, 2022)

Detection and diversity of grapevine virus L from a Vitis cultivar collection in Stellenbosch, South Africa - David A. Read; Genevieve D. Thompson; Dirk Swanevelder; Gerhard Pietersen (European Journal of Plant Pathology, 2021)

Lung inflammation from repeated exposure to LPS and glyphosate - Upkardeep Pandher; Shelley Kirychuk; David Schneberger; Brooke Thompson; Gurpreet Aulakh; R. S. Sethi; Baljit Singh (Cell and Tissue Research, 2021)

Detecting forest response to droughts with global observations of vegetation water content - Alexandra G. Konings; Sassan S. Saatchi; Christian Frankenberg; Michael Keller; Victor Leshyk; William R. L. Anderegg; Vincent Humphrey; Ashley M. Matheny; Anna Trugman; Lawren Sack; Elizabeth Agee; Mallory L. Barnes; et al. (Global Change Biology, 2021)
Droughts in a warming climate have become more common and more extreme, making understanding forest responses to water stress increasingly pressing. Analysis of water stress in trees has long focused on water potential in xylem and leaves, which influences stomatal closure and water flow through the soil‐plant‐atmosphere continuum. At the same time, changes of vegetation water content (VWC) are linked to a range of tree responses, including fluxes of water and carbon, mortality, flammability, and more. Unlike water potential, which requires demanding in situ measurements, VWC can be retrieved from remote sensing measurements, particularly at microwave frequencies using radar and radiometry. Here, we highlight key frontiers through which VWC has the potential to significantly increase our understanding of forest responses to water stress. To validate remote sensing observations of VWC at landscape scale and to better relate them to data assimilation model parameters, we introduce an ecosystem‐scale analog of the pressure–volume curve, the non‐linear relationship between average leaf or branch water potential and water content commonly used in plant hydraulics. The sources of variability in these ecosystem‐scale pressure‐volume curves and their relationship to forest response to water stress are discussed. We further show to what extent diel, seasonal, and decadal dynamics of VWC reflect variations in different processes relating the tree response to water stress. VWC can also be used for inferring belowground conditions—which are difficult to impossible to observe directly. Lastly, we discuss how a dedicated geostationary spaceborne observational system for VWC, when combined with existing datasets, can capture diel and seasonal water dynamics to advance the science and applications of global forest vulnerability to future droughts.

Ethics and governance for internet‐based conservation science research - Ruth M. Thompson; Jordan Hall; Chris Morrison; Nicole R. Palmer; David L. Roberts (Conservation Biology, 2021)
Internet‐based research is increasingly important for conservation science and has wide‐ranging applications and contexts, including culturomics, illegal wildlife trade, and citizen science. However, online research methods pose a range of ethical and legal challenges. Online data may be protected by copyright, database rights, or contract law. Privacy rights may also restrict the use and access of data, as well as ethical requirements from institutions. Online data have real‐world meaning, and the ethical treatment of individuals and communities must not be marginalized when conducting internet‐based research. As ethics frameworks originally developed for biomedical applications are inadequate for these methods, we propose that research activities involving the analysis of preexisting online data be treated analogous to offline social science methods, in particular, nondeceptive covert observation. By treating internet users and their data with respect and due consideration, conservationists can uphold the public trust needed to effectively address real‐world issues.

On the appropriate and inappropriate uses of probability distributions in climate projections and some alternatives - Joel Katzav; Erica L. Thompson; James Risbey; David A. Stainforth; Seamus Bradley; Mathias Frisch (Climatic Change, 2021)

Untangling local and remote influences in two major petrel habitats in the oligotrophic Southern Ocean - Daniel C. Jones; Filipe R. Ceia; Eugene Murphy; Karine Delord; Robert W. Furness; Ariane Verdy; Matthew Mazloff; Richard A. Phillips; Paul M. Sagar; Jean‐Baptiste Sallée; Ben Schreiber; David R. Thompson; et al. (Global Change Biology, 2021)
Ocean circulation connects geographically distinct ecosystems across a wide range of spatial and temporal scales via exchanges of physical and biogeochemical properties. Remote oceanographic processes can be especially important for ecosystems in the Southern Ocean, where the Antarctic Circumpolar Current transports properties across ocean basins through both advection and mixing. Recent tracking studies have indicated the existence of two large‐scale, open ocean habitats in the Southern Ocean used by grey petrels ( Procellaria cinerea ) from two populations (i.e., Kerguelen and Antipodes islands) during their nonbreeding season for extended periods during austral summer (i.e., October to February). In this work, we use a novel combination of large‐scale oceanographic observations, surface drifter data, satellite‐derived primary productivity, numerical adjoint sensitivity experiments, and output from a biogeochemical state estimate to examine local and remote influences on these grey petrel habitats. Our aim is to understand the oceanographic features that control these isolated foraging areas and to evaluate their ecological value as oligotrophic open ocean habitats. We estimate the minimum local primary productivity required to support these populations to be much

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

Novel viruses associated with plants of the family Amaryllidaceae in South Africa - David A. Read; Ronel Roberts; Dirk Swanevelder; Gerhard Pietersen; Genevieve D. Thompson (Archives of Virology, 2021)

Using Remote Sensing and in situ Measurements for Efficient Mapping and Optimal Sampling of Coral Reefs - Alberto Candela; Kevin Edelson; Michelle M. Gierach; David R. Thompson; Gail Woodward; David Wettergreen (Frontiers in Marine Science, 2021)
Coral reefs are of undeniable importance to the environment, yet little is known of them on a global scale. Assessments rely on laborious, local in-water surveys. In recent years remote sensing has been useful on larger scales for certain aspects of reef science such as benthic functional type discrimination. However, remote sensing only gives indirect information about reef condition. Only through combination of remote sensing and in situ data can we achieve coverage to understand reef condition and monitor worldwide condition. This work presents an approach to global mapping of coral reef condition that intelligently selects local, in situ measurements that refine the accuracy and resolution of global remote sensing. To this end, we apply new techniques in remote sensing analysis, probabilistic modeling for coral reef mapping, and decision theory for sample selection. Our strategy represents a fundamental change in how we study coral reefs and assess their condition on a global scale. We demonstrate feasibility and performance of our approach in a proof of concept using spaceborne remote sensing together with high-quality airborne data from the NASA Earth Venture Suborbital-2 (EVS-2) Coral Reef Airborne Laboratory (CORAL) mission as a proxy for in situ samples. Results indicate that our method is capable of extrapolating in situ features and refining information from remote sensing with increasing accuracy. Furthermore, the results confirm that decision theory is a powerful tool for sample selection.

Cystic fibrosis improves COVID-19 survival and provides clues for treatment of SARS-CoV-2 - Edward H. Abraham; Guido Guidotti; Eliezer Rapaport; David Bower; Jack Brown; Robert J. Griffin; Andrew Donnelly; Ellen D. Waitzkin; Kenon Qamar; Mark A. Thompson; Sukumar Ethirajan; Kent Robinson (Purinergic Signalling, 2021)
Systemic pools of ATP are elevated in individuals homozygous for cystic fibrosis (CF) as evidenced by elevated blood and plasma ATP levels. This elevated ATP level seems to provide benefit in the presence of advanced solid tumors (Abraham et al., Nature Medicine 2(5):593–596, 1996). We published in this journal a paper showing that IV ATP can elevate the depleted ATP pools of advanced cancer patients up to levels found in CF patients with subsequent clinical, biochemical, and quality of life (QOL) improvements (Rapaport et al., Purinergic Signalling 11(2): 251–262, 2015). We hypothesize that the elevated ATP levels seen in CF patients may be benefiting CF patients in another way: by improving their survival after contracting COVID-19. We discuss here the reasoning behind this hypothesis and suggest how these findings might be applied clinically in the general population.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Genomic characterization of two novel viruses infecting Barleria cristata L. from the genera Orthotospovirus and Polerovirus - David A. Read; Ronel Roberts; Genevieve Thompson (Archives of Virology, 2021)

A double pedigree reveals genetic but not cultural inheritance of cooperative personalities in wild banded mongooses - Hazel J. Nichols; Kevin Arbuckle; Jennifer L. Sanderson; Emma I. K. Vitikainen; Harry H. Marshall; Faye J. Thompson; Michael A. Cant; David A. Wells (Ecology Letters, 2021)
Personality traits, such as the propensity to cooperate, are often inherited from parents to offspring, but the pathway of inheritance is unclear. Traits could be inherited via genetic or parental effects, or culturally via social learning from role models. However, these pathways are difficult to disentangle in natural systems as parents are usually the source of all of these effects. Here, we exploit natural ‘cross fostering’ in wild banded mongooses to investigate the inheritance of cooperative behaviour. Our analysis of 800 adult helpers over 21 years showed low but significant genetic heritability of cooperative personalities in males but not females. Cross fostering revealed little evidence of cultural heritability: offspring reared by particularly cooperative helpers did not become more cooperative themselves. Our results demonstrate that cooperative personalities are not always highly heritable in wild, and that the basis of behavioural traits can vary within a species (here, by sex).

Design, Development, In Vitro and Preliminary In Vivo Evaluation of a Novel Photo-Angioplasty Device: Lumi-Solve - HongBin Liu; Gopal R. Sama; Andrea Robinson; Simon Mountford; Philip E. Thompson; Andrew Rodda; John Forsythe; Patrick J. Mornane; Paul Pasic; Helmut Thissen; Melissa Byrne; David M. Kaye; et al. (Cardiovascular Engineering and Technology, 2021)

Pulling Back the Blue Curtain: A Pelagic Monitoring Program for the Blue Belt - Jessica Jane Meeuwig; Christopher David Harburn Thompson; John Andrew Forrest; Hanna Jabour Christ; Tom Bech Letessier; Dirk Jason Meeuwig (Frontiers in Marine Science, 2021)
Ocean health is fundamental to human prosperity. However, fisheries exploitation, industrialization and climate change imperil our oceans. Marine protected areas (MPAs) have been established in coastal habitats since the 1970s and the ongoing monitoring of these MPAs has shown their general ecological and economic value. Demonstrable benefits can include biodiversity conservation, fisheries enhancement and climate resilience. Since the 2000s, large scale MPAs (LSMPAs) are increasingly established, with new parks including extensive areas of pelagic habitat. Seminal was the British Indian Ocean Territory (BIOT) MPA created in 2010. In 2016, the United Kingdom Government established the Blue Belt Programme to provide long-term protection of the marine environment across the United Kingdom Overseas Territories and LSMPAs have now been established or designated in a number of these territories. However, empirical data for the Blue Belt LSMPAs are needed to test their effectiveness in conserving pelagic species and to allow managers to monitor and assess the LSMPAs based on the best available evidence. This Perspective presents current advances in video-based monitoring of pelagic wildlife and provides examples of key ecological insights gained from their use that are relevant to LSMPA planning and management. We present a case study from the BIOT MPA and finally generalize with respect to key learning’s that will support planning and monitoring of LSMPAs within the Blue Belt Programme.

ReNovRisk: a multidisciplinary programme to study the cyclonic risks in the South-West Indian Ocean - Pierre Tulet; Bertrand Aunay; Guilhem Barruol; Christelle Barthe; Remi Belon; Soline Bielli; François Bonnardot; Olivier Bousquet; Jean-Pierre Cammas; Julien Cattiaux; Fabrice Chauvin; Idriss Fontaine; et al. (Natural Hazards, 2021)
Today, resilience in the face of cyclone risks has become a crucial issue for our societies. With climate change, the risk of strong cyclones occurring is expected to intensify significantly and to impact the way of life in many countries. To meet some of the associated challenges, the interdisciplinary ReNovRisk programme aims to study tropical cyclones and their impacts on the South-West Indian Ocean basin. This article is a presentation of the ReNovRisk programme, which is divided into four areas: study of cyclonic hazards, study of erosion and solid transport processes, study of water transfer and swell impacts on the coast, and studies of socio-economic impacts. The first transdisciplinary results of the programme are presented together with the database, which will be open access from mid-2021.

Host recognition by Rhinocyllus conicus of floral scents from invasive and threatened thistles - Ikju Park; David C. Thompson (Biological Invasions, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

First report of Catharanthus mosaic virus infecting Gomphocarpus physocarpus in South Africa - David A. Read; Ronel Roberts; Genevieve D. Thompson (Journal of Plant Pathology, 2021)

Orchid fleck virus and a novel strain of sweet potato chlorotic stunt virus associated with an ornamental cultivar of Alcea rosea L. in South Africa - David A. Read; Ronel Roberts; Genevieve D. Thompson (European Journal of Plant Pathology, 2021)

Exposure to Intermittent Noise Exacerbates the Cardiovascular Response of Wistar–Kyoto Rats to Ozone Inhalation and Arrhythmogenic Challenge - Mehdi S. Hazari; Kaitlyn Phillips; Kimberly M. Stratford; Malek Khan; Leslie Thompson; Wendy Oshiro; George Hudson; David W. Herr; Aimen K. Farraj (Cardiovascular Toxicology, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Overview of PAX gene family: analysis of human tissue-specific variant expression and involvement in human disease - Brian Thompson; Emily A. Davidson; Wei Liu; Daniel W. Nebert; Elspeth A. Bruford; Hongyu Zhao; Emmanouil T. Dermitzakis; David C. Thompson; Vasilis Vasiliou (Human Genetics, 2021)

Effects of temperature on sexual development in steelhead, Oncorhynchus mykiss - Kathleen S. Cole; David L. G. Noakes; Neil Thompson; Michael Blouin; Bruce Morrison; Ryan B. Couture; Joseph O’Neil; Carl B. Schreck (Environmental Biology of Fishes, 2021)

No differences in delay discounting between smokers with and without HIV - Cory Czuczman; Morgan Thompson; E. Paul Wileyto; Robert Schnoll; David Metzger; Frank Leone; Karam Mounzer; Robert Gross; Rebecca L. Ashare (Psychopharmacology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

On-Field Performance of an Instrumented Mouthguard for Detecting Head Impacts in American Football - Lee F. Gabler; Samuel H. Huddleston; Nathan Z. Dau; David J. Lessley; Kristy B. Arbogast; Xavier Thompson; Jacob E. Resch; Jeff R. Crandall (Annals of Biomedical Engineering, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Learning to be an interdisciplinary researcher: incorporating training about dispositional and epistemological differences into graduate student environmental science teams - David C. Gosselin; Kate Thompson; Deana Pennington; Shirley Vincent (Journal of Environmental Studies and Sciences, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Differential responses of heather and red grouse to long-term spatio-temporal variation in sheep grazing - Sonja C. Ludwig; Nicholas J. Aebischer; Michael Richardson; Staffan Roos; Des B. A. Thompson; Jeremy D. Wilson; David Baines (Biodiversity and Conservation, 2020)

A large population-based investigation into the genetics of susceptibility to gastrointestinal infections and the link between gastrointestinal infections and mental illness - Ron Nudel; Vivek Appadurai; Andrew J. Schork; Alfonso Buil; Jonas Bybjerg-Grauholm; Anders D. Børglum; Mark J. Daly; Ole Mors; David M. Hougaard; Preben Bo Mortensen; Thomas Werge; Merete Nordentoft; et al. (Human Genetics, 2020)
Gastrointestinal infections can be life threatening, but not much is known about the host’s genetic contribution to susceptibility to gastrointestinal infections or the latter’s association with psychiatric disorders. We utilized iPSYCH, a genotyped population-based sample of individuals born between 1981 and 2005 comprising 65,534 unrelated Danish individuals (45,889 diagnosed with mental disorders and 19,645 controls from a random population sample) in which all individuals were linked utilizing nationwide population-based registers to estimate the genetic contribution to susceptibility to gastrointestinal infections, identify genetic variants associated with gastrointestinal infections, and examine the link between gastrointestinal infections and psychiatric and neurodevelopmental disorders. The SNP heritability of susceptibility to gastrointestinal infections ranged from 3.7% to 6.4% on the liability scale. Significant correlations were found between gastrointestinal infections and the combined group of mental disorders (OR = 2.09; 95% CI: 1.82–2.4, P = 1.87 × 10 –25 ). Correlations with autism spectrum disorder, attention deficit hyperactivity disorder, and depression were also significant. We identified a genome-wide significant locus associated with susceptibility to gastrointestinal infections (OR = 1.13; 95% CI: 1.08–1.18, P = 2.9 × 10 –8 ), where the top SNP was an eQTL for the ABO gene. The risk allele was associated with reduced ABO expression, providing, for the first time, genetic evidence to support previous studies linking the O blood group to gastrointestinal infections. This study also highlights the importance of integrative work in genetics, psychiatry, infection, and epidemiology on the road to translational medicine.

Metaviromic analysis reveals coinfection of papaya in western Kenya with a unique strain of Moroccan watermelon mosaic virus and a novel member of the family Alphaflexiviridae - David Alan Read; John Muoma; Genevieve Dawn Thompson (Archives of Virology, 2020)

Weather underground: Subsurface hydrologic processes mediate tree vulnerability to extreme climatic drought - Blair C. McLaughlin; Rachel Blakey; Andrew P. Weitz; Xue Feng; Brittni J. Brown; David D. Ackerly; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2020)
Drought extent and severity have increased and are predicted to continue to increase in many parts of the world. Understanding tree vulnerability to drought at both individual and species levels is key to ongoing forest management and preparation for future transitions in community composition. The influence of subsurface hydrologic processes is particularly important in water‐limited ecosystems, and is an under‐studied aspect of tree drought vulnerability. With California's 2013–2016 extraordinary drought as a natural experiment, we studied four co‐occurring woodland tree species, blue oak ( Quercus douglasii ), valley oak ( Quercus lobata ), gray pine ( Pinus sabiniana ), and California juniper ( Juniperus californica ), examining drought vulnerability as a function of climate, lithology and hydrology using regional aerial dieback surveys and site‐scale field surveys. We found that in addition to climatic drought severity (i.e., rainfall), subsurface processes explained variation in drought vulnerability within and across species at both scales. Regionally for blue oak, severity of dieback was related to the bedrock lithology, with higher mortality on igneous and metamorphic substrates, and to regional reductions in groundwater. At the site scale, access to deep subsurface water, evidenced by stem water stable isotope composition, was related to canopy condition across all species. Along hillslope gradients, channel locations supported similar environments in terms of water stress across a wide climatic gradient, indicating that subsurface hydrology mediates species’ experience of drought, and that areas associated with persistent access to subsurface hydrologic resources may provide important refugia at species’ xeric range edges. Despite this persistent overall influence of the subsurface environment, individual species showed markedly different response patterns. We argue that hydrologic niche segregation can be a useful lens through which to interpret these differences in vulnerability to climatic drought and climate change.

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Rapid recovery of ecosystem function following extreme drought in a South African savanna grassland - Kevin R. Wilcox; Sally E. Koerner; David L. Hoover; Andrea K. Borkenhagen; Deron E. Burkepile; Scott L. Collins; Ava M. Hoffman; Kevin P. Kirkman; Alan K. Knapp; Tercia Strydom; Dave I. Thompson; Melinda D. Smith (Ecology, 2020)
Climatic extremes, such as severe drought, are expected to increase in frequency and magnitude with climate change. Thus, identifying mechanisms of resilience is critical to predicting the vulnerability of ecosystems. An exceptional drought (

Fast‐start escape performance across temperature and salinity gradients in mummichog Fundulus heteroclitus - David C. Collar; Jessica S. Thompson; Tyler C. Ralston; Trevor J. Hobbs (Journal of Fish Biology, 2020)
Fast‐start predator‐escape performance of mummichogs Fundulus heteroclitus was tested across field‐informed variation in temperature (24, 30 and 36°C) and salinity (2, 12 and 32 ppt). Performance was similar across temperatures and salinities when fish were allowed to acclimate to these conditions. However, when mummichogs experienced acute temperature changes, performance exhibited thermal dependence in two contrasting ways. Fast‐start turning rates and linear speeds varied directly with the temperature at which the manoeuvre was executed, but these aspects of performance varied inversely with acclimation temperature, with cool‐acclimated fish exhibiting faster starts across test temperatures. Temperature effects were consistent across salinities. These results suggest that while mummichogs increase performance with acute temperature increases, long‐term rises in sea temperature may cause these fish to become more susceptible to predation during abrupt cooling events, such as when storm events flood shallow water estuaries with cool rainwater.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Risk Management and Analytics in Wildfire Response - Matthew P. Thompson; Yu Wei; David E. Calkin; Christopher D. O’Connor; Christopher J. Dunn; Nathaniel M. Anderson; John S. Hogland (Current Forestry Reports, 2019)
Purpose of Review The objectives of this paper are to briefly review basic risk management and analytics concepts, describe their nexus in relation to wildfire response, demonstrate real-world application of analytics to support response decisions and organizational learning, and outline an analytics strategy for the future. Recent Findings Analytics can improve decision-making and organizational performance across a variety of areas from sports to business to real-time emergency response. A lack of robust descriptive analytics on wildfire incident response effectiveness is a bottleneck for developing operationally relevant and empirically credible predictive and prescriptive analytics to inform and guide strategic response decisions. Capitalizing on technology such as automated resource tracking and machine learning algorithms can help bridge gaps between monitoring, learning, and data-driven decision-making. Summary By investing in better collection, documentation, archiving, and analysis of operational data on response effectiveness, fire management organizations can promote systematic learning and provide a better evidence base to support response decisions. We describe an analytics management framework that can provide structure to help deploy analytics within organizations, and provide real-world examples of advanced fire analytics applied in the USA. To fully capitalize on the potential of analytics, organizations may need to catalyze cultural shifts that cultivate stronger appreciation for data-driven decision processes, and develop informed skeptics that effectively balance both judgment and analysis in decision-making.

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Production and ecosystem structure in cold‐core vs. warm‐core eddies: Implications for the zooplankton isoscape and rock lobster larvae - Anya M. Waite; Eric Raes; Lynnath E. Beckley; Peter A. Thompson; David Griffin; Megan Saunders; Christin Säwström; Richard O'Rorke; Miao Wang; Jason P. Landrum; Andrew Jeffs (Limnology and Oceanography, 2019)
Anticyclonic (warm‐core) mesoscale eddies (WCEs) in the Eastern Indian Ocean carry higher surface chlorophyll signatures than cyclonic (cold‐core) eddies (CCEs). Paradoxically, WCEs host rock lobster larvae (phyllosomas) with lower lipid stores and protein reserves than phyllosomas in CCEs, suggesting a poorer nutritional status. We assess primary productivity and zooplankton isotopic data from eight eddies across four research voyages (2003–2011) to determine how this contradiction might occur. We find that WCEs and CCEs are equally productive per unit chlorophyll a , but depth‐integrated primary production (PP) is greater in eddies with shallower mixed layers (MLs), especially in CCEs. MLs tend to be shallower in CCEs than in WCEs because the pycnocline is closer to the surface. This, in combination with stronger stratification in CCE euphotic zones than those of WCEs, supports greater flagellate and dinoflagellate populations in CCEs. These phytoplankton provide high‐quality nutrition for zooplankton, which feed on average ~ 0.6 trophic level lower in CCEs with the shallowest MLs, accumulating high lipid stores. Conversely, WCEs have, on average, ~ 70 m deeper MLs than CCEs, and host a phytoplankton community with more diatoms. Diatoms provide lower quality food for zooplankton, and zooplankton lipid stores in WCEs decline with trophic level, and possibly, with time after initial (or seasonal) nutrient injection. As a result, phyllosomas in CCEs have higher energy and lipid content than those in warm‐core eddies. The resolution of the paradox, therefore, is that the higher surface chlorophyll signatures of WCEs are not representative of the nutritional value of the prey field of the phyllosoma. We also conclude that interannual variations of mixed layer depth occur at a regional scale, controlling PP.

Validation of Tidal Stream Turbine Wake Predictions and Analysis of Wake Recovery Mechanism - Sanchit Salunkhe; Oumnia El Fajri; Shanti Bhushan; David Thompson; Daphne O’Doherty; Tim O’Doherty; Allan Mason-Jones (Journal of Marine Science and Engineering, 2019)
This paper documents the predictive capability of rotating blade-resolved unsteady Reynolds averaged Navier-Stokes (URANS) and Improved Delayed Detached Eddy Simulation (IDDES) computations for tidal stream turbine performance and intermediate wake characteristics. Ansys/Fluent and OpenFOAM simulations are performed using mixed-cell, unstructured grids consisting of up to 11 million cells. The thrust, power and intermediate wake predictions compare reasonably well within 10% of the experimental data. For the wake predictions, OpenFOAM performs better than Ansys/Fluent, and IDDES better than URANS when the resolved turbulence is triggered. The primary limitation of the simulations is under prediction of the wake diffusion towards the turbine axis, which in return is related to the prediction of turbulence in the tip-vortex shear layer. The shear-layer involves anisotropic turbulent structures; thus, hybrid RANS/LES models, such as IDDES, are preferred over URANS. Unfortunately, IDDES fails to accurately predict the resolved turbulence in the near-wake region due to the modeled stress depletion issue.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

A resting state fMRI analysis pipeline for pooling inference across diverse cohorts: an ENIGMA rs-fMRI protocol - Bhim M. Adhikari; Neda Jahanshad; Dinesh Shukla; Jessica Turner; Dominik Grotegerd; Udo Dannlowski; Harald Kugel; Jennifer Engelen; Bruno Dietsche; Axel Krug; Tilo Kircher; Els Fieremans; et al. (Brain Imaging and Behavior, 2019)

Genomics detects population structure within and between ocean basins in a circumpolar seabird: The white‐chinned petrel - Kalinka Rexer‐Huber; Andrew J. Veale; Paulo Catry; Yves Cherel; Ludovic Dutoit; Yasmin Foster; John C. McEwan; Graham C. Parker; Richard A. Phillips; Peter G. Ryan; Andrew J. Stanworth; Tracey van Stijn; et al. (Molecular Ecology, 2019)
The Southern Ocean represents a continuous stretch of circumpolar marine habitat, but the potential physical and ecological drivers of evolutionary genetic differentiation across this vast ecosystem remain unclear. We tested for genetic structure across the full circumpolar range of the white‐chinned petrel ( Procellaria aequinoctialis ) to unravel the potential drivers of population differentiation and test alternative population differentiation hypotheses. Following range‐wide comprehensive sampling, we applied genomic (genotyping‐by‐sequencing or GBS; 60,709 loci) and standard mitochondrial‐marker approaches (cytochrome b and first domain of control region) to quantify genetic diversity within and among island populations, test for isolation by distance, and quantify the number of genetic clusters using neutral and outlier (non‐neutral) loci. Our results supported the multi‐region hypothesis, with a range of analyses showing clear three‐region genetic population structure, split by ocean basin, within two evolutionary units. The most significant differentiation between these regions confirmed previous work distinguishing New Zealand and nominate subspecies. Although there was little evidence of structure within the island groups of the Indian or Atlantic oceans, a small set of highly‐discriminatory outlier loci could assign petrels to ocean basin and potentially to island group, though the latter needs further verification. Genomic data hold the key to revealing substantial regional genetic structure within wide‐ranging circumpolar species previously assumed to be panmictic.

Reconciling the contribution of environmental and stochastic structuring of tropical forest diversity through the lens of imaging spectroscopy - Boris Bongalov; David F. R. P. Burslem; Tommaso Jucker; Samuel E. D. Thompson; James Rosindell; Tom Swinfield; Reuben Nilus; Daniel Clewley; Oliver L. Phillips; David A. Coomes (Ecology Letters, 2019)
Both niche and stochastic dispersal processes structure the extraordinary diversity of tropical plants, but determining their relative contributions has proven challenging. We address this question using airborne imaging spectroscopy to estimate canopy β‐diversity for an extensive region of a Bornean rainforest and challenge these data with models incorporating niches and dispersal. We show that remotely sensed and field‐derived estimates of pairwise dissimilarity in community composition are closely matched, proving the applicability of imaging spectroscopy to provide β‐diversity data for entire landscapes of over 1000 ha containing contrasting forest types. Our model reproduces the empirical data well and shows that the ecological processes maintaining tropical forest diversity are scale dependent. Patterns of β‐diversity are shaped by stochastic dispersal processes acting locally whilst environmental processes act over a wider range of scales.

Uses for humanised mouse models in precision medicine for neurodegenerative disease - Remya R. Nair; Silvia Corrochano; Samanta Gasco; Charlotte Tibbit; David Thompson; Cheryl Maduro; Zeinab Ali; Pietro Fratta; Abraham Acevedo Arozena; Thomas J. Cunningham; Elizabeth M. C. Fisher (Mammalian Genome, 2019)
Neurodegenerative disease encompasses a wide range of disorders afflicting the central and peripheral nervous systems and is a major unmet biomedical need of our time. There are very limited treatments, and no cures, for most of these diseases, including Alzheimer’s Disease, Parkinson's Disease, Huntington Disease, and Motor Neuron Diseases. Mouse and other animal models provide hope by analysing them to understand pathogenic mechanisms, to identify drug targets, and to develop gene therapies and stem cell therapies. However, despite many decades of research, virtually no new treatments have reached the clinic. Increasingly, it is apparent that human heterogeneity within clinically defined neurodegenerative disorders, and between patients with the same genetic mutations, significantly impacts disease presentation and, potentially, therapeutic efficacy. Therefore, stratifying patients according to genetics, lifestyle, disease presentation, ethnicity, and other parameters may hold the key to bringing effective therapies from the bench to the clinic. Here, we discuss genetic and cellular humanised mouse models, and how they help in defining the genetic and environmental parameters associated with neurodegenerative disease, and so help in developing effective precision medicine strategies for future healthcare.

Characterization and detection of maize-associated pteridovirus (MaPV), infecting maize (Zea mays) in the Arusha region of Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest Mbega (European Journal of Plant Pathology, 2019)

Whole cell inactivated autogenous vaccine effectively protects red Nile tilapia ( Oreochromis niloticus ) against francisellosis via intraperitoneal injection - José Gustavo Ramírez‐Paredes; Miguel Angel Mendoza‐Roldan; Benjamin Lopez‐Jimena; Khalid Shahin; Matthijs Metselaar; Kim D. Thompson; David J. Penman; Randolph H. Richards; Alexandra Adams (Journal of Fish Diseases, 2019)
Francisella noatunensis subsp. orientalis is a pathogen of tilapia and other warm‐water fish for which no vaccines are commercially available. In this study, a whole cell formalin‐inactivated vaccine was developed for the first time using the highly virulent isolate STIR‐GUS‐F2f7 and the oil‐based adjuvant Montanide™ ISA 763A VG. The efficacy of the vaccine was assessed in red Nile tilapia via intraperitoneal (i.p.) injection using homologous experimental infection and correlates of protection such as seral antibody production and bacterial loads in the spleen. For immunization, fish were i.p. injected with 0.1 ml of the vaccine, the adjuvant alone or PBS. At 840 degree days post‐vaccination, all fish were i.p. injected with 4.0 × 10 3 CFU/fish of pathogenic bacteria. The RPS at the end of the trial was 100% in the vaccinated group with significantly higher survival than in the adjuvant and control groups. The RPS in the adjuvant group was 42%, and no significant difference was seen in survival between this and the PBS group. Moreover, significantly higher antibody titres in the serum and significantly lower bacterial loads in the spleen were detected in the vaccinated fish by ELISA and qPCR, respectively. These findings highlight the potential of autogenous vaccines for controlling francisellosis in tilapia.

A dual rescaled Mitscherlich model of the simultaneous savings in phosphorus and zinc fertiliser from arbuscular mycorrhizal fungal colonisation of linseed (Linum usitatissimum L.) - Nicole P. Seymour; David G. Edwards; John P. Thompson (Plant and Soil, 2019)

Diversity and distribution of Maize-associated totivirus strains from Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Virus Genes, 2019)

Molecular characterization of Morogoro maize-associated virus, a nucleorhabdovirus detected in maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Archives of Virology, 2019)

Retrieval of Atmospheric Parameters and Surface Reflectance from Visible and Shortwave Infrared Imaging Spectroscopy Data - David R. Thompson; Luis Guanter; Alexander Berk; Bo-Cai Gao; Rudolf Richter; Daniel Schläpfer; Kurtis J. Thome (Surveys in Geophysics, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Can gypsy moth stand the heat? A reciprocal transplant experiment with an invasive forest pest across its southern range margin - Trevor M. Faske; Lily M. Thompson; Nana Banahene; Andi Levorse; Melisa Quiroga Herrera; Kayla Sherman; Sarah E. Timko; Banruo Yang; David R. Gray; Dylan Parry; Patrick C. Tobin; Andrew J. Eckert; et al. (Biological Invasions, 2019)

Molecular identification of Botryosphaeria dothidea as a fungal associate of the gall midge Asphondylia prosopidis on mesquite in the United States - Ikju Park; Soum Sanogo; Stephen F. Hanson; David C. Thompson (BioControl, 2019)

First report of maize yellow mosaic virus (MaYMV) on maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherstone; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingston Mashingaidze; Dave Kenneth Berger; Tanya Welgemoed; Gerhard Pietersen; Susanna Elizabeth Schulze; Barnabas Kiula; et al. (Journal of Plant Pathology, 2019)

Cephalopod component of Snares Penguin (Eudyptes robustus) at Snares Islands, New Zealand in the 1980´s: relationships with local fisheries and implications on the penguin’s conservation - Hugo Guímaro; David Thompson; Vitor Paiva; Duncan Cunningham; Philip Moors; José Xavier (Frontiers in Marine Science, 2019)

Dynamics of Prochlorococcus Diversity and Photoacclimation During Short-Term Shifts in Water Column Stratification at Station ALOHA - Anne W. Thompson; Ger van den Engh; Nathan A. Ahlgren; Kathleen Kouba; Samantha Ward; Samuel T. Wilson; David M. Karl (Frontiers in Marine Science, 2018)

Seabed Mining and Approaches to Governance of the Deep Seabed - Kirsten F. Thompson; Kathryn A. Miller; Duncan Currie; Paul Johnston; David Santillo (Frontiers in Marine Science, 2018)

The ecohydrological context of drought and classification of plant responses - Xue Feng; David D. Ackerly; Todd E. Dawson; Stefano Manzoni; Rob P. Skelton; Giulia Vico; Sally E. Thompson (Ecology Letters, 2018)
Many recent studies on drought‐induced vegetation mortality have explored how plant functional traits, and classifications of such traits along axes of, for example, isohydry–anisohydry, might contribute to predicting drought survival and recovery. As these studies proliferate, the consistency and predictive value of such classifications need to be carefully examined. Here, we outline the basis for a systematic classification of plant drought responses that accounts for both environmental conditions and functional traits. We use non‐dimensional analysis to integrate plant traits and metrics of environmental variation into groups that can be associated with alternative drought stress pathways (hydraulic failure and carbon limitation), and demonstrate that these groupings predict physiological drought outcomes using both synthetic and measured data. In doing so, we aim to untangle some confounding effects of environment and trait variations that undermine current classification schemes, advocate for more careful treatment of the environmental context within which plants experience and respond to drought, and outline a pathway towards a general classification of drought vulnerability.

Human Neural Stem Cell Extracellular Vesicles Improve Tissue and Functional Recovery in the Murine Thromboembolic Stroke Model - Robin L. Webb; Erin E. Kaiser; Shelley L. Scoville; Tyler A. Thompson; Sumbul Fatima; Chirayukumar Pandya; Karishma Sriram; Raymond L. Swetenburg; Kumar Vaibhav; Ali S. Arbab; Babak Baban; Krishnan M. Dhandapani; et al. (Translational Stroke Research, 2018)

Coated-Platelet Trends Predict Short-Term Clinical OutcomeAfter Subarachnoid Hemorrhage - Bappaditya Ray; Vijay M. Pandav; Eleanor A. Mathews; David M. Thompson; Lance Ford; Lori K. Yearout; Bradley N. Bohnstedt; Shuchi Chaudhary; George L. Dale; Calin I. Prodan (Translational Stroke Research, 2018)

Computational Models of Polymer Synthesis Driven by Dehydration/Rehydration Cycles: Repurination in Simulated Hydrothermal Fields - Mason Hargrave; Spencer K. Thompson; David Deamer (Journal of Molecular Evolution, 2018)

Evaluating cognition and thermal physiology as components of the pace-of-life syndrome - Celine T. Goulet; Marcus Michelangeli; Melinda Chung; Julia L. Riley; Bob B. M. Wong; Michael B. Thompson; David G. Chapple (Evolutionary Ecology, 2018)

Clinical Translation of the LevelCheck Decision Support Algorithm for Target Localization in Spine Surgery - Amir Manbachi; Tharindu De Silva; Ali Uneri; Matthew Jacobson; Joseph Goerres; Michael Ketcha; Runze Han; Nafi Aygun; David Thompson; Xiaobu Ye; Sebastian Vogt; Gerhard Kleinszig; et al. (Annals of Biomedical Engineering, 2018)

Correction to: Down from the treetops: red langur (Presbytis rubicunda) terrestrial behavior - Susan M. Cheyne; Supiansyah; Adul; Claire J. Neale; Carolyn Thompson; Cara H. Wilcox; Yvette C. Ehlers Smith; David A. Ehlers Smith (Primates, 2018)

Down from the treetops: red langur (Presbytis rubicunda) terrestrial behavior - Susan M. Cheyne; Supiansyah; Adul; Claire J. Neale; Carolyn Thompson; Cara H. Wilcox; Yvette C. Ehlers Smith; David A. Ehlers Smith (Primates, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Biogeography of pelagic food webs in the North Pacific - John F. Piatt; Mayumi L. Arimitsu; William J. Sydeman; Sarah Ann Thompson; Heather Renner; Stephani Zador; David Douglas; Scott Hatch; Arthur Kettle; Jeff Williams (Fisheries Oceanography, 2018)
The tufted puffin ( Fratercula cirrhata ) is a generalist seabird that breeds throughout the North Pacific and eats more than 75 different prey species. Using puffins as samplers, we characterized the geographic variability in pelagic food webs across the subarctic North Pacific from the composition of ~10,000 tufted puffin meals (~56,000 prey items) collected at 35 colonies in the Gulf of Alaska (GoA) and Aleutian Archipelago. Cluster analysis of diet species composition suggested three distinct forage fish communities: (i) in the northern GoA, multiple age‐classes of coastal and shelf residents such as capelin, sand lance and herring dominated the food web, (ii) in the western GoA to eastern Aleutians, the shelf community was dominated by transient age‐0 walleye pollock, and (iii) in the western Aleutians, shelf‐edge and mesopelagic forage species such as squid, lanternfish, and Atka mackerel were prevalent. Geographic patterns of abundance of capelin and sand lance in tufted puffin diets were corroborated by independent research fisheries and diets of piscivorous fish, indicating that puffin diets reflect the local abundance of forage species, not just selection of favored species. Generalized additive models showed that habitat characteristics predict, in a non‐linear fashion, forage species distribution and abundance across two large marine ecosystems. We conclude that major biogeographic patterns in forage fish distribution follow gradients in key habitat features, and puffin diets reflect those patterns.

Rethinking the Wildland Fire Management System - Matthew P Thompson; Donald G MacGregor; Christopher J Dunn; David E Calkin; John Phipps (Journal of Forestry, 2018)

Correction to: Anaphylactoid Reactions to Intravenous N-Acetylcysteine during Treatment for Acetaminophen Poisoning - Mark Yarema; Puja Chopra; Marco L. A. Sivilotti; David Johnson; Alberto Nettel-Aguirre; Benoit Bailey; Charlemaigne Victorino; Sophie Gosselin; Roy Purssell; Margaret Thompson; Daniel Spyker; Barry Rumack (Journal of Medical Toxicology, 2018)

Anaphylactoid Reactions to Intravenous N-Acetylcysteine during Treatment for Acetaminophen Poisoning - Mark Yarema; Puja Chopra; Marco L. A. Sivilotti; David Johnson; Alberto Nettel-Aguirre; Benoit Bailey; Charlemaigne Victorino; Sophie Gosselin; Roy Purssell; Margaret Thompson; Daniel Spyker; Barry Rumack (Journal of Medical Toxicology, 2018)

Ecological risk, demography and technological complexity in the Late Pleistocene of northern Malawi: implications for geographical patterning in the Middle Stone Age - Jessica C. Thompson; Alexander Mackay; Sheila Nightingale; David Wright; Jeong‐Heon Choi; Menno Welling; Hari Blackmore; Elizabeth Gomani‐Chindebvu (Journal of Quaternary Science, 2018)
The Late Pleistocene Middle Stone Age (MSA) record of Africa provides early examples of standardised stone tool production and complex manufacturing sequences, superficially implying a long‐term trend towards greater complexity in MSA technology at a continental scale. However, at this scale, spatial and temporal expressions of technological complexity are uneven. New lithic and chronometric data from the East–Central African record add further regional perspective to these patterns. Stone artefact assemblages from Karonga, northern, Malawi (92–22 ka), persistently lack the complexity demonstrated elsewhere in Africa at the same times, despite similar lithic raw materials. These new data provide an essential avenue for exploring hypotheses about the roles of environmental risk and demography in shaping the expression of MSA technology across the continent, not just at a local scale. When set within this framework, the simplicity of the Karonga MSA is best explained by its position in an environment that was persistently low in relative extrinsic subsistence risk. These results reinforce that motivations to invest in complex tools were variable through space and time, and that this variation, more than factors relating to behavioural capacity, may explain the patchy evidence for lithic complexity in the later MSA.

Thermal biology mediates responses of amphibians and reptiles to habitat modification - A. Justin Nowakowski; James I. Watling; Michelle E. Thompson; George A. Brusch; Alessandro Catenazzi; Steven M. Whitfield; David J. Kurz; Ángela Suárez‐Mayorga; Andrés Aponte‐Gutiérrez; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2018)
Human activities often replace native forests with warmer, modified habitats that represent novel thermal environments for biodiversity. Reducing biodiversity loss hinges upon identifying which species are most sensitive to the environmental conditions that result from habitat modification. Drawing on case studies and a meta‐analysis, we examined whether observed and modelled thermal traits, including heat tolerances, variation in body temperatures, and evaporative water loss, explained variation in sensitivity of ectotherms to habitat modification. Low heat tolerances of lizards and amphibians and high evaporative water loss of amphibians were associated with increased sensitivity to habitat modification, often explaining more variation than non‐thermal traits. Heat tolerances alone explained 24–66% (mean = 38%) of the variation in species responses, and these trends were largely consistent across geographic locations and spatial scales. As habitat modification alters local microclimates, the thermal biology of species will likely play a key role in the reassembly of terrestrial communities.

An Overview of Seabed Mining Including the Current State of Development, Environmental Impacts, and Knowledge Gaps - Kathryn A. Miller; Kirsten F. Thompson; Paul Johnston; David Santillo (Frontiers in Marine Science, 2018)

Forest biodiversity, ecosystem functioning and the provision of ecosystem services - Eckehard G. Brockerhoff; Luc Barbaro; Bastien Castagneyrol; David I. Forrester; Barry Gardiner; José Ramón González-Olabarria; Phil O’B. Lyver; Nicolas Meurisse; Anne Oxbrough; Hisatomo Taki; Ian D. Thompson; Fons van der Plas; et al. (Biodiversity and Conservation, 2017)

Sex‐specific shifts in morphology and colour pattern polymorphism during range expansion of an invasive lizard - Kimberly A. Miller; Andressa Duran; Jane Melville; Michael B. Thompson; David G. Chapple (Journal of Biogeography, 2017)
Aim Human‐assisted range expansion of animals to new environments can lead to phenotypic shifts over ecological time‐scales. We investigated whether phenotypic changes are sex‐specific using an invasive lizard ( Lampropholis delicata ). Location Pacific region (Hawaiian Islands, Lord Howe Island, New Zealand, eastern Australia). Methods Using our knowledge of the introduction history of L. delicata , we examined museum specimens of individuals collected across the native and introduced range to determine whether shifts in morphology or colour pattern polymorphism had occurred during its range expansion, and if so, whether they differed between the sexes. Results Sexual dimorphism in both size and shape was documented within the native range of the delicate skink. However, during range expansion, phenotypic shifts were observed in shape, but not size. In two of the three invasive populations, these phenotypic shifts were sex‐specific. In the Hawaiian Islands, changes in shape were driven by males, whereas in New Zealand it was due to shifts in females. Similarly, changes in the frequency of a colour pattern polymorphism, a mid‐lateral stripe shown to have sex‐specific impacts on fitness (positive in females, negative in males), occurred following colonization of the Hawaiian Islands and Lord Howe Island. In Hawaii, the incidence of the polymorphism increased over time in females, and decreased in males. Main conclusions Phenotypic shifts during the range expansion of invasive species may be sex‐specific, and are potentially related to the degree of realized niche shift that has occurred between the source and introduced range.

Dynamics of Prochlorococcus and Synechococcus at Station ALOHA Revealed through Flow Cytometry and High-Resolution Vertical Sampling - Ger J. van den Engh; Joseph K. Doggett; Anne W. Thompson; Martina A. Doblin; Carla N. G. Gimpel; David M. Karl (Frontiers in Marine Science, 2017)

Transcriptomic profiling of adaptive responses to ocean acidification - Priscila Goncalves; David B. Jones; Emma L. Thompson; Laura M. Parker; Pauline M. Ross; David A. Raftos (Molecular Ecology, 2017)
Some populations of marine organisms appear to have inherent tolerance or the capacity for acclimation to stressful environmental conditions, including those associated with climate change. Sydney rock oysters from the B2 breeding line exhibit resilience to ocean acidification ( OA ) at the physiological level. To understand the molecular basis of this physiological resilience, we analysed the gill transcriptome of B2 oysters that had been exposed to near‐future projected ocean pH over two consecutive generations. Our results suggest that the distinctive performance of B2 oysters in the face of OA is mediated by the selective expression of genes involved in multiple cellular processes. Subsequent high‐throughput qPCR revealed that some of these transcriptional changes are exclusive to B2 oysters and so may be associated with their resilience to OA . The intracellular processes mediated by the differentially abundant genes primarily involve control of the cell cycle and maintenance of cellular homeostasis. These changes may enable B2 oysters to prevent apoptosis resulting from oxidative damage or to alleviate the effects of apoptosis through regulation of the cell cycle. Comparative analysis of the OA conditioning effects across sequential generations supported the contention that B2 and wild‐type oysters have different trajectories of changing gene expression and responding to OA . Our findings reveal the broad set of molecular processes underlying transgenerational conditioning and potential resilience to OA in a marine calcifier. Identifying the mechanisms of stress resilience can uncover the intracellular basis for these organisms to survive and thrive in a rapidly changing ocean.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Steep effort discounting of a preferred reward over a freely-available option in prolonged methamphetamine withdrawal in male rats - Andrew B. Thompson; Julian Gerson; Alexandra Stolyarova; Amador Bugarin; Evan E. Hart; J. David Jentsch; Alicia Izquierdo (Psychopharmacology, 2017)

Rapid divergence of animal personality and syndrome structure across an arid-aquatic habitat matrix - Nicholas P. Moran; Krystina D. Mossop; Ross M. Thompson; David G. Chapple; Bob B. M. Wong (Oecologia, 2017)

Optimizing Biomass Feedstock Blends with Respect to Cost, Supply, and Quality for Catalyzed and Uncatalyzed Fast Pyrolysis Applications - Vicki S. Thompson; John E. Aston; Jeffrey A. Lacey; David N. Thompson (BioEnergy Research, 2017)

High occurrence of jellyfish predation by black‐browed and Campbell albatross identified by DNA metabarcoding - Julie C. McInnes; Rachael Alderman; Mary‐Anne Lea; Ben Raymond; Bruce E. Deagle; Richard A. Phillips; Andrew Stanworth; David R. Thompson; Paulo Catry; Henri Weimerskirch; Cristián G. Suazo; Michaël Gras; et al. (Molecular Ecology, 2017)
Gelatinous zooplankton are a large component of the animal biomass in all marine environments, but are considered to be uncommon in the diet of most marine top predators. However, the diets of key predator groups like seabirds have conventionally been assessed from stomach content analyses, which cannot detect most gelatinous prey. As marine top predators are used to identify changes in the overall species composition of marine ecosystems, such biases in dietary assessment may impact our detection of important ecosystem regime shifts. We investigated albatross diet using DNA metabarcoding of scats to assess the prevalence of gelatinous zooplankton consumption by two albatross species, one of which is used as an indicator species for ecosystem monitoring. Black‐browed and Campbell albatross scats were collected from eight breeding colonies covering the circumpolar range of these birds over two consecutive breeding seasons. Fish was the main dietary item at most sites; however, cnidarian DNA , primarily from scyphozoan jellyfish, was present in 42% of samples overall and up to 80% of samples at some sites. Jellyfish was detected during all breeding stages and consumed by adults and chicks. Trawl fishery catches of jellyfish near the Falkland Islands indicate a similar frequency of jellyfish occurrence in albatross diets in years of high and low jellyfish availability, suggesting jellyfish consumption may be selective rather than opportunistic. Warmer oceans and overfishing of finfish are predicted to favour jellyfish population increases, and we demonstrate here that dietary DNA metabarcoding enables measurements of the contribution of gelatinous zooplankton to the diet of marine predators.

Reconciling seasonal hydraulic risk and plant water use through probabilistic soil–plant dynamics - Xue Feng; Todd E. Dawson; David D. Ackerly; Louis S. Santiago; Sally E. Thompson (Global Change Biology, 2017)
Current models used for predicting vegetation responses to climate change are often guided by the dichotomous needs to resolve either (i) internal plant water status as a proxy for physiological vulnerability or (ii) external water and carbon fluxes and atmospheric feedbacks. Yet, accurate representation of fluxes does not always equate to accurate predictions of vulnerability. We resolve this discrepancy using a hydrodynamic framework that simultaneously tracks plant water status and water uptake. We couple a minimalist plant hydraulics model with a soil moisture model and, for the first time, translate rainfall variability at multiple timescales – with explicit descriptions at daily, seasonal, and interannual timescales – into a physiologically meaningful metric for the risk of hydraulic failure. The model, parameterized with measured traits from chaparral species native to Southern California, shows that apparently similar transpiration patterns throughout the dry season can emerge from disparate plant water potential trajectories, and vice versa. The parsimonious set of parameters that captures the role of many traits across the soil–plant–atmosphere continuum is then used to establish differences in species sensitivities to shifts in seasonal rainfall statistics, showing that co‐occurring species may diverge in their risk of hydraulic failure despite minimal changes to their seasonal water use. The results suggest potential shifts in species composition in this region due to species‐specific changes in hydraulic risk. Our process‐based approach offers a quantitative framework for understanding species sensitivity across multiple timescales of rainfall variability and provides a promising avenue toward incorporating interactions of temporal variability and physiological mechanisms into drought response models.

Hydrologic refugia, plants, and climate change - Blair C. McLaughlin; David D. Ackerly; P. Zion Klos; Jennifer Natali; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2017)
Climate, physical landscapes, and biota interact to generate heterogeneous hydrologic conditions in space and over time, which are reflected in spatial patterns of species distributions. As these species distributions respond to rapid climate change, microrefugia may support local species persistence in the face of deteriorating climatic suitability. Recent focus on temperature as a determinant of microrefugia insufficiently accounts for the importance of hydrologic processes and changing water availability with changing climate. Where water scarcity is a major limitation now or under future climates, hydrologic microrefugia are likely to prove essential for species persistence, particularly for sessile species and plants. Zones of high relative water availability – mesic microenvironments – are generated by a wide array of hydrologic processes, and may be loosely coupled to climatic processes and therefore buffered from climate change. Here, we review the mechanisms that generate mesic microenvironments and their likely robustness in the face of climate change. We argue that mesic microenvironments will act as species‐specific refugia only if the nature and space/time variability in water availability are compatible with the ecological requirements of a target species. We illustrate this argument with case studies drawn from California oak woodland ecosystems. We posit that identification of hydrologic refugia could form a cornerstone of climate‐cognizant conservation strategies, but that this would require improved understanding of climate change effects on key hydrologic processes, including frequently cryptic processes such as groundwater flow.

Robustness of a model microbial community emerges from population structure among single cells of a clonal population - Anne W. Thompson; Serdar Turkarslan; Christina E. Arens; Adrián López García de Lomana; Arjun V. Raman; David A. Stahl; Nitin S. Baliga (Environmental Microbiology, 2017)
Summary Microbial populations can withstand, overcome and persist in the face of environmental fluctuation. Previously, we demonstrated how conditional gene regulation in a fluctuating environment drives dilution of condition‐specific transcripts, causing a population of Desulfovibrio vulgaris Hildenborough (DvH) to collapse after repeatedly transitioning from sulfate respiration to syntrophic conditions with the methanogen Methanococcus maripaludis . Failure of the DvH to successfully transition contributed to the collapse of this model community. We investigated the mechanistic basis for loss of robustness by examining whether conditional gene regulation altered heterogeneity in gene expression across individual DvH cells. We discovered that robustness of a microbial population across environmental transitions was attributable to the retention of cells in two states that exhibited different condition‐specific gene expression patterns. In our experiments, a population with disrupted conditional regulation successfully alternated between cell states. Meanwhile, a population with intact conditional regulation successfully switched between cell states initially, but collapsed after repeated transitions, possibly due to the high energy requirements of regulation. These results demonstrate that the survival of this entire model microbial community is dependent on the regulatory system's influence on the distribution of distinct cell states among individual cells within a clonal population.

Continental-scale convection-permitting modeling of the current and future climate of North America - Changhai Liu; Kyoko Ikeda; Roy Rasmussen; Mike Barlage; Andrew J. Newman; Andreas F. Prein; Fei Chen; Liang Chen; Martyn Clark; Aiguo Dai; Jimy Dudhia; Trude Eidhammer; et al. (Climate Dynamics, 2017)

Tracking reveals limited interactions between Campbell Albatross and fisheries during the breeding season - Lisa A. Sztukowski; Mariëlle L. van Toor; Henri Weimerskirch; David R. Thompson; Leigh G. Torres; Paul M. Sagar; Peter A. Cotton; Stephen C. Votier (Journal of Ornithology, 2017)

Volume 30 Issue 02 View Issue TOC Volume 30, No. 2 Satellites to Seafloor: Toward Fully Autonomous Ocean Sampling - Andrew Thompson; Yi Chao; Steve Chien; James Kinsey; M. Mar Flexas; Zachary Erickson; John Farrara; David Fratantoni; Andrew Branch; Selina Chu; Martina Troesch; Brian Claus; et al. (Oceanography, 2017)

White-chinned petrel population estimate, Disappointment Island (Auckland Islands) - Kalinka Rexer-Huber; Graham C. Parker; Paul M. Sagar; David R. Thompson (Polar Biology, 2017)

Predation by New Zealand sea lions and Brown Skuas is causing the continued decline of an Eastern Rockhopper Penguin colony on Campbell Island - Kyle W. Morrison; Doug P. Armstrong; Phil F. Battley; Sarah E. Jamieson; David R. Thompson (Polar Biology, 2017)

Pedigree Reconstruction with Genome-Wide Markers in Potato - Jeffrey B. Endelman; Cari A. Schmitz Carley; David S. Douches; Joseph J. Coombs; Benoit Bizimungu; Walter S. De Jong; Kathleen G. Haynes; David G. Holm; J. Creighton Miller; Richard G. Novy; Jiwan P. Palta; David L. Parish; et al. (American Journal of Potato Research, 2017)

Process Simulation and Cost Analysis for Removing Inorganics from Wood Chips Using Combined Mechanical and Chemical Preprocessing - Hongqiang Hu; Tyler L. Westover; Robert Cherry; John E. Aston; Jeffrey A. Lacey; David N. Thompson (BioEnergy Research, 2017)

Demography and ecology of southern right whales Eubalaena australis wintering at sub-Antarctic Campbell Island, New Zealand - Leigh G. Torres; Will Rayment; Carlos Olavarría; David R. Thompson; Brittany Graham; C. Scott Baker; Nathalie Patenaude; Sarah Jane Bury; Laura Boren; Graham Parker; Emma L. Carroll (Polar Biology, 2017)

Rapid transcriptional acclimation following transgenerational exposure of oysters to ocean acidification - Priscila Goncalves; Kelli Anderson; Emma L. Thompson; Aroon Melwani; Laura m. Parker; Pauline M. Ross; David A. Raftos (Molecular Ecology, 2016)
Marine organisms need to adapt in order to cope with the adverse effects of ocean acidification and warming. Transgenerational exposure to CO 2 stress has been shown to enhance resilience to ocean acidification in offspring from a number of species. However, the molecular basis underlying such adaptive responses is currently unknown. Here, we compared the transcriptional profiles of two genetically distinct oyster breeding lines following transgenerational exposure to elevated CO 2 in order to explore the molecular basis of acclimation or adaptation to ocean acidification in these organisms. The expression of key target genes associated with antioxidant defence, metabolism and the cytoskeleton was assessed in oysters exposed to elevated CO 2 over three consecutive generations. This set of target genes was chosen specifically to test whether altered responsiveness of intracellular stress mechanisms contributes to the differential acclimation of oyster populations to climate stressors. Transgenerational exposure to elevated CO 2 resulted in changes to both basal and inducible expression of those key target genes (e.g. ec SOD , catalase and peroxiredoxin 6), particularly in oysters derived from the disease‐resistant, fast‐growing B2 line. Exposure to CO 2 stress over consecutive generations produced opposite and less evident effects on transcription in a second population that was derived from wild‐type (nonselected) oysters. The analysis of key target genes revealed that the acute responses of oysters to CO 2 stress appear to be affected by population‐specific genetic and/or phenotypic traits and by the CO 2 conditions to which their parents had been exposed. This supports the contention that the capacity for heritable change in response to ocean acidification varies between oyster breeding lines and is mediated by parental conditioning.

Genetic distinctiveness of the damselfly Coenagrion puella in North Africa: an overlooked and endangered taxon - Sónia Ferreira; Jean-Pierre Boudot; Mohamed El Haissoufi; Paulo Célio Alves; David J. Thompson; José Carlos Brito; Phillip C. Watts (Conservation Genetics, 2016)

Anxiety is related to indices of cortical maturation in typically developing children and adolescents - Erik Newman; Wesley K. Thompson; Hauke Bartsch; Donald J. Hagler; Chi-Hua Chen; Timothy T. Brown; Joshua M. Kuperman; Connor McCabe; Yoonho Chung; Ondrej Libiger; Natacha Akshoomoff; Cinnamon S. Bloss; et al. (Brain Structure and Function, 2016)

Distribution of Prochlorococcus Ecotypes in the Red Sea Basin Based on Analyses of rpoC1 Sequences - Ahmed A. Shibl; Mohamed F. Haroon; David K. Ngugi; Luke R. Thompson; Ulrich Stingl (Frontiers in Marine Science, 2016)

Acute high-intensity interval rowing increases thrombin generation in healthy men - Matthew J. Sedgwick; Matthew Thompson; Jack Garnham; Alice E. Thackray; Laura A. Barrett; Matthew Powis; David J. Stensel (European Journal of Applied Physiology, 2016)

Barriers to Innovation in Urban Wastewater Utilities: Attitudes of Managers in California - Michael Kiparsky; Barton H. Thompson; Christian Binz; David L. Sedlak; Lars Tummers; Bernhard Truffer (Environmental Management, 2016)

The EMBeRS project: employing model-based reasoning in socio-environmental synthesis - Deana Pennington; Gabriele Bammer; Antje Danielson; David Gosselin; Julia Gouvea; Geoffrey Habron; Dave Hawthorne; Roderic Parnell; Kate Thompson; Shirley Vincent; Cynthia Wei (Journal of Environmental Studies and Sciences, 2016)

The canalized parental roles of a Eudyptes penguin constrain provisioning and growth of chicks during nutritional stress - Kyle W. Morrison; Neil C. Morrison; Raymond M. Buchheit; Rob Dunn; Phil F. Battley; David R. Thompson (Behavioral Ecology and Sociobiology, 2016)

Timber Harvesting Behaviour in Massachusetts, USA: Does Price Matter to Private Landowners? - David B. Kittredge; Jonathan R. Thompson (Small-scale Forestry, 2016)

Habitat and trophic ecology of Antarctic squid: Where do young and adults live and what do they eat? - Queirós José; Cherel Yves; Hilário Ana; Thompson David; Walker Kath; Elliott Graeme; Xavier Jose (Frontiers in Marine Science, 2016)

Biofilm formation in an experimental water distribution system: the contamination of non-touch sensor taps and the implication for healthcare - Ginny Moore; David Stevenson; Katy-Anne Thompson; Simon Parks; Didier Ngabo; Allan M. Bennett; Jimmy T. Walker (Biofouling, 2015)

Human ALDH1B1 Polymorphisms may Affect the Metabolism of Acetaldehyde and All-trans retinaldehyde—In Vitro Studies and Computational Modeling - Brian C. Jackson; Philip Reigan; Bettina Miller; David C. Thompson; Vasilis Vasiliou (Pharmaceutical Research, 2015)

Microbial taxonomy in the post-genomic era: Rebuilding from scratch? - Cristiane C. Thompson; Gilda R. Amaral; Mariana Campeão; Robert A. Edwards; Martin F. Polz; Bas E. Dutilh; David W. Ussery; Tomoo Sawabe; Jean Swings; Fabiano L. Thompson (Archives of Microbiology, 2015)

Transcriptional Regulatory Events Initiated by Ascl1 and Neurog2 During Neuronal Differentiation of P19 Embryonic Carcinoma Cells - Holly S. Huang; Tanya M. Redmond; Ginger M. Kubish; Shweta Gupta; Robert C. Thompson; David L. Turner; Michael D. Uhler (Journal of Molecular Neuroscience, 2015)

Population dynamics of Eastern Rockhopper Penguins on Campbell Island in relation to sea surface temperature 1942–2012: current warming hiatus pauses a long-term decline - Kyle W. Morrison; Phil F. Battley; Paul M. Sagar; David R. Thompson (Polar Biology, 2015)

Call for a California Coccidioidomycosis Consortium to Face the Top Ten Challenges Posed by a Recalcitrant Regional Disease - George R. Thompson III; David A. Stevens; Karl V. Clemons; Josh Fierer; Royce H. Johnson; Jane Sykes; George Rutherford; Michael Peterson; John W. Taylor; Vishnu Chaturvedi (Mycopathologia, 2015)

A tree well travelled: global genetic structure of the invasive tree Acacia saligna - Genevieve D. Thompson; Dirk U. Bellstedt; David M. Richardson; John R. U. Wilson; Johannes J. Le Roux (Journal of Biogeography, 2015)
Aim Invasiveness of an introduced species in one region is often used to predict risk and inform management of the same species elsewhere. This assumes that entities in both regions are equivalent in their ecology and response to management. However, intraspecific genetic variation can result in differences in performance between regions. We conducted population genetic and phylogeographic analyses of the widely introduced and intraspecifically diverse Australian tree species Acacia saligna, in order to improve our understanding of its worldwide invasion history. Location The native range of A. saligna in Western Australia and introduced ranges in eastern Australia, Israel, Italy, New Zealand, Portugal, South Africa, Spain and the USA . Methods We analysed microsatellite genotype data obtained from 447 individuals of A. saligna (including reference populations of known subspecies lineages) using Bayesian assignment analysis. We also reconstructed parsimony networks and a phylogeny using data from the nuclear external transcribed spacer (ETS) gene region for a subset of 120 individuals. Results There was no consistent genetic pattern in introduced populations in different parts of the world. All three subspecies lineages of A. saligna have been moved around the world, showing high levels of admixture in some introduced populations. A previously identified novel and cultivated South African lineage was also identified in Portugal and Italy. Main conclusions With different subspecies lineages present in different regions globally, it is unclear exactly how effective management approaches of invasions in one region will be in other regions. For example, the successful biological control agents against cultivated lineages of A. saligna in South Africa will probably be effective against similar genotypes in Portugal but not against dissimilar lineages present elsewhere. Further work is needed to conclusively link the relative extent of invasions to genetic differences, and to determine whether genetic novelty can explain the widespread invasions of A. saligna observed in South Africa and Portugal.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Higher trophic level prey does not represent a higher quality diet in a threatened seabird: implications for relating population dynamics to diet shifts inferred from stable isotopes - Kyle W. Morrison; Sarah J. Bury; David R. Thompson (Marine Biology, 2014)

Sedentary behavior is associated with colorectal adenoma recurrence in men - Christine L. Sardo Molmenti; Elizabeth A. Hibler; Erin L. Ashbeck; Cynthia A. Thomson; David O. Garcia; Denise Roe; Robin B. Harris; Peter Lance; Martin Cisneroz; Maria Elena Martinez; Patricia A. Thompson; Elizabeth T. Jacobs (Cancer Causes & Control, 2014)

Biodiversity and ecosystem services: lessons from nature to improve management of planted forests for REDD-plus - Ian D. Thompson; Kimiko Okabe; John A. Parrotta; Eckehard Brockerhoff; Hervé Jactel; David I. Forrester; Hisatomo Taki (Biodiversity and Conservation, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genetic analysis of quantitative phenotypes in AD and MCI: imaging, cognition and biomarkers - Li Shen; Paul M. Thompson; Steven G. Potkin; Lars Bertram; Lindsay A. Farrer; Tatiana M. Foroud; Robert C. Green; Xiaolan Hu; Matthew J. Huentelman; Sungeun Kim; John S. K. Kauwe; Qingqin Li; et al. (Brain Imaging and Behavior, 2014)

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients - Katie H. Owens; Philip G. M. Murphy; Natalie J. Medlicott; Julia Kennedy; Mathew Zacharias; Neil Curran; Sree Sreebhavan; Mark Thompson-Fawcett; David M. Reith (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Remote Antarctic feeding ground important for east Australian humpback whales - Rochelle Constantine; Debbie Steel; Judy Allen; Megan Anderson; Olive Andrews; C. Scott Baker; Peta Beeman; Daniel Burns; Jean-Benoît Charrassin; Simon Childerhouse; Michael Double; Paul Ensor; et al. (Marine Biology, 2014)

Bottom side‐roll feeding by humpback whales ( Megaptera novaeangliae ) in the southern Gulf of Maine, U.S.A - Colin Ware; David N. Wiley; Ari S. Friedlaender; Mason Weinrich; Elliott L. Hazen; Alessandro Bocconcelli; Susan E. Parks; Alison K. Stimpert; Mike A. Thompson; Kyler Abernathy (Marine Mammal Science, 2014)
Humpback whales (Megaptera novaeangliae) are known for the variety and complexity of their feeding behaviors. Here we report on the use of synchronous motion and acoustic recording tags ( DTAG s) to provide the first detailed kinematic descriptions of humpback whales using bottom side‐rolls ( BSR s) to feed along the seafloor. We recorded 3,505 events from 19 animals (individual range 8–722). By animal, mean BSR duration ranged from 14.1 s to 36.2 s.; mean body roll angle from 80º to 121º, and mean pitch from 7º to 38º. The median interval between sequential BSR s, by animal, ranged from 24.0 s to 63.6 s and animals tended to maintain a consistent BSR heading during long BSR series encompassing multiple dives. BSR s were most frequent between 2200 and 0400. We identify three classes of behavior: simple side‐roll, side‐roll inversion, and repetitive scooping. Results indicate that BSR feeding is a common technique in the study area and there is both coordination and noncoordination between animals. We argue that this behavior is not lunge feeding as normally characterized, because animals are moving slowly through the event. The behavior also leads to vulnerability to entanglement in bottom‐set fishing gear, a major mortality factor for the species.

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Colony social structure in native and invasive populations of the social wasp Vespula pensylvanica - Cause Hanna; Erin D. Cook; Ariel R. Thompson; Lyndzey E. Dare; Amanda L. Palaski; David Foote; Michael A. D. Goodisman (Biological Invasions, 2014)

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Bergmann's rule is maintained during a rapid range expansion in a damselfly - Christopher Hassall; Simon Keat; David J. Thompson; Phillip C. Watts (Global Change Biology, 2014)
Climate‐induced range shifts result in the movement of a sample of genotypes from source populations to new regions. The phenotypic consequences of those shifts depend upon the sample characteristics of the dispersive genotypes, which may act to either constrain or promote phenotypic divergence, and the degree to which plasticity influences the genotype–environment interaction. We sampled populations of the damselfly Erythromma viridulum from northern Europe to quantify the phenotypic (latitude–body size relationship based on seven morphological traits) and genetic (variation at microsatellite loci) patterns that occur during a range expansion itself. We find a weak spatial genetic structure that is indicative of high gene flow during a rapid range expansion. Despite the potentially homogenizing effect of high gene flow, however, there is extensive phenotypic variation among samples along the invasion route that manifests as a strong, positive correlation between latitude and body size consistent with Bergmann's rule. This positive correlation cannot be explained by variation in the length of larval development (voltinism). While the adaptive significance of latitudinal variation in body size remains obscure, geographical patterns in body size in odonates are apparently underpinned by phenotypic plasticity and this permits a response to one or more environmental correlates of latitude during a range expansion.

How flies respond to honey bee pheromone: the role of the foraging gene on reproductive response to queen mandibular pheromone - Alison L. Camiletti; David N. Awde; Graham J. Thompson (The Science of Nature, 2014)

State-space modelling reveals proximate causes of harbour seal population declines - Jason Matthiopoulos; Line Cordes; Beth Mackey; David Thompson; Callan Duck; Sophie Smout; Marjolaine Caillat; Paul Thompson (Oecologia, 2014)

Somatic embryogenesis in forestry with a focus on Europe: state-of-the-art, benefits, challenges and future direction - Marie-Anne Lelu-Walter; David Thompson; Luc Harvengt; Leopoldo Sanchez; Mariano Toribio; Luc E. Pâques (Tree Genetics & Genomes, 2013)

Modelling the impact of urbanisation on regional climate in the Greater London Area - David Grawe; Heather L. Thompson; Jennifer A. Salmond; Xiao‐Ming Cai; K. Heinke Schlünzen (International Journal of Climatology, 2013)
Urban areas have well‐documented effects on climate, such as the urban heat island (UHI) effect, reduction of wind speeds, enhanced turbulence and boundary layer heights, and changes in cloud cover and precipitation. The aim of this study is to quantify the impact of the urban area of London on local and regional climate. This is achieved through the coupling of the non‐hydrostatic mesoscale model METRAS with the sophisticated urban canopy scheme BEP. The model is configured for case studies of the London region, for typical UHI conditions, and the model results are evaluated using data from meteorological monitoring sites. This study develops a methodology to quantify the regional impact of urbanisation from numerical model results. The urban area, in its current form, is found to affect near surface temperature, the diurnal temperature range, the UHI, and the near surface wind speed and direction. For the selected cases, peak UHI intensities of up to 2.5 K are found during night time hours, with the timing and magnitude of the peak showing good agreement with previous experimental studies for London. The timing of the UHI peak intensity for the current urban land cover for London shows a good agreement with the results of measurements. A significant reduction in wind speed over the urban area was also simulated during both daytime and night time, due to the higher roughness of the city compared to the rural domain. The effect is shown to have a regional character, with both urban and surrounding rural areas demonstrating a significant impact. Thus, the UHI can not only be understood when focussing on local data, but the interaction with the surrounding needs to be considered.

Subantimicrobial-dose doxycycline treatment increases serum cholesterol efflux capacity from macrophages - Aino Salminen; Pirkko J. Pussinen; Jeffrey B. Payne; Julie A. Stoner; Matti Jauhiainen; Lorne M. Golub; Hsi-Ming Lee; David M. Thompson; Timo Sorsa (Inflammation Research, 2013)

Analysis of fatty acids and fatty alcohols reveals seasonal and sex-specific changes in the diets of seabirds - Ellie Owen; Francis Daunt; Colin Moffat; David A. Elston; Sarah Wanless; Paul Thompson (Marine Biology, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Fire in the Air: Biomass Burning Impacts in a Changing Climate - Melita Keywood; Maria Kanakidou; Andreas Stohl; Frank Dentener; Giacomo Grassi; C. P. Meyer; Kjetil Torseth; David Edwards; Anne M. Thompson; Ulrike Lohmann; John Burrows (Critical Reviews in Environmental Science and Technology, 2013)

Inheritance of resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) in five doubled-haploid populations of wheat - John P. Thompson; Rebecca S. Zwart; David Butler (Euphytica, 2012)

Probabilistic assessment of wildfire hazard and municipal watershed exposure - Joe Scott; Don Helmbrecht; Matthew P. Thompson; David E. Calkin; Kate Marcille (Natural Hazards, 2012)

Mikrobielle Ökologie des Roten Meeres - Uli Stingl; David Kamanda Ngugi; Luke Thompson; Andre Antunes; Matthew Cahill (BIOspektrum, 2012)

Phylogenetic and functional alpha and beta diversity in temperate and tropical tree communities - Nathan G. Swenson; David L. Erickson; Xiangcheng Mi; Norman A. Bourg; Jimena Forero-Montaña; Xuejun Ge; Robert Howe; Jeffrey K. Lake; Xiaojuan Liu; Keping Ma; Nancai Pei; Jill Thompson; et al. (Ecology, 2012)
The study of biodiversity has tended to focus primarily on relatively information‐poor measures of species diversity. Recently, many studies of local diversity (alpha diversity) have begun to use measures of functional and phylogenetic alpha diversity. Investigations into the phylogenetic and functional dissimilarity (beta diversity) of communities have been far less numerous, but these dissimilarity measures have the potential to infer the mechanisms underlying community assembly and dynamics. Here, we relate levels of phylogenetic and functional alpha diversity to levels of phylogenetic and functional beta diversity to infer the mechanism or mechanisms responsible for the assembly of tree communities in six forests located in tropical and temperate latitudes. The results show that abiotic filtering plays a role in structuring local assemblages and governing spatial turnover in community composition and that phylogenetic measures of alpha and beta diversity are not strong predictors of functional alpha and beta diversity in the forests studied.

Cultivation shapes genetic novelty in a globally important invader - GENEVIEVE D. THOMPSON; DIRK U. BELLSTEDT; MARGARET BYRNE; MELISSA A. MILLAR; DAVID M. RICHARDSON; JOHN R.U. WILSON; JOHANNES J. LE ROUX (Molecular Ecology, 2012)
Acacia saligna is a species complex that has become invasive in a number of countries worldwide where it has caused substantial environmental and economic impacts. Understanding genetic and other factors contributing to its success may allow managers to limit future invasions of closely related species. We used three molecular markers to compare the introduced range (South Africa) to the native range (Western Australia). Nuclear markers showed that invasive populations are divergent from native populations and most closely related to a cultivated population in Western Australia. We also found incongruence between nuclear and chloroplast data that, together with the long history of cultivation of the species, suggest that introgressive hybridization (coupled with chloroplast capture) may have occurred within A. saligna. While we could not definitively prove introgression, the genetic distance between cultivated and native A. saligna populations was comparable to known interspecific divergences among other Acacia species. Therefore, cultivation, multiple large‐scale introductions and possibly introgressive hybridization have rapidly given rise to the divergent genetic entity present in South Africa. This may explain the known global variation in invasiveness and inaccuracy of native bioclimatic models in predicting potential distributions.

Reduced investment in immune function in invasion-front populations of the cane toad (Rhinella marina) in Australia - David Llewellyn; Michael B. Thompson; Gregory P. Brown; Benjamin L. Phillips; Richard Shine (Biological Invasions, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Global threats to pinnipeds - Kit M. Kovacs; Alex Aguilar; David Aurioles; Vladimir Burkanov; Claudio Campagna; Nick Gales; Tom Gelatt; Simon D. Goldsworthy; Simon J. Goodman; Greg J. G. Hofmeyr; Tero Härkönen; Lloyd Lowry; et al. (Marine Mammal Science, 2012)

Temporal turnover in the composition of tropical tree communities: functional determinism and phylogenetic stochasticity - Nathan G. Swenson; James C. Stegen; Stuart J. Davies; David L. Erickson; Jimena Forero-Montaña; Allen H. Hurlbert; W. John Kress; Jill Thompson; María Uriarte; S. Joseph Wright; Jess K. Zimmerman (Ecology, 2012)
The degree to which turnover in biological communities is structured by deterministic or stochastic factors and the identities of influential deterministic factors are fundamental, yet unresolved, questions in ecology. Answers to these questions are particularly important for projecting the fate of forests with diverse disturbance histories worldwide. To uncover the processes governing turnover we use species‐level molecular phylogenies and functional trait data sets for two long‐term tropical forest plots with contrasting disturbance histories: one forest is older‐growth, and one was recently disturbed. Having both phylogenetic and functional information further allows us to parse out the deterministic influences of different ecological filters. With the use of null models we find that compositional turnover was random with respect to phylogeny on average, but highly nonrandom with respect to measured functional traits. Furthermore, as predicted by a deterministic assembly process, the older‐growth and disturbed forests were characterized by less than and greater than expected functional turnover, respectively. These results suggest that the abiotic environment, which changes due to succession in the disturbed forest, strongly governs the temporal dynamics of disturbed and undisturbed tropical forests. Predicting future changes in the composition of disturbed and undisturbed forests may therefore be tractable when using a functional‐trait‐based approach.

Study design and mark-recapture estimates of dispersal: a case study with the endangered damselfly Coenagrion mercuriale - Christopher Hassall; David John Thompson (Journal of Insect Conservation, 2012)

Far-field effects of tidal energy extraction in the Minas Passage on tidal circulation in the Bay of Fundy and Gulf of Maine using a nested-grid coastal circulation model - Daisuke Hasegawa; Jinyu Sheng; David A. Greenberg; Keith R. Thompson (Ocean Dynamics, 2011)

Field estimates of reproductive success in a model insect: behavioural surrogates are poor predictors of fitness - David J. Thompson; Christopher Hassall; Chris D. Lowe; Phillip C. Watts (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 905–913 Abstract Understanding, and therefore measuring, factors that determine fitness is a central problem in evolutionary biology. We studied a natural population of Coenagrion puella (Odonata: Zygoptera) over two entire breeding seasons, with over a thousand individuals uniquely marked and genotyped, and all mating events at the rendezvous site recorded. Using a parentage analysis, fitness of individuals in the first generation was quantified as the numbers of offspring that survived to maturity. Although mating behaviour can be predicted by environmental and demographical variables, the numbers of mature offspring produced (fitness) cannot, and crucially, are poorly correlated with behavioural observations of mating. While fitness of both sexes was positively related to mating behaviour and to female’s ectoparasite burden, these behavioural observations explained little more variance in offspring production than environmental and demographical variables. Thus, we demonstrate that behavioural measures of reproductive success are not necessarily reliable estimates of fitness in natural populations.

Integrated national-scale assessment of wildfire risk to human and ecological values - Matthew P. Thompson; David E. Calkin; Mark A. Finney; Alan A. Ager; Julie W. Gilbertson-Day (Stochastic Environmental Research and Risk Assessment, 2011)

Advancing effects analysis for integrated, large-scale wildfire risk assessment - Matthew P. Thompson; David E. Calkin; Julie W. Gilbertson-Day; Alan A. Ager (Environmental Monitoring and Assessment, 2011)

Simulating the three-dimensional circulation and hydrography of Halifax Harbour using a multi-nested coastal ocean circulation model - Shiliang Shan; Jinyu Sheng; Keith Richard Thompson; David Alexander Greenberg (Ocean Dynamics, 2011)

Sex-specific effect of aging on submaximal leg exercise hemodynamics in middle-aged and older adults - Beth Parker; Jeffrey Capizzi; Amanda Augeri; Adam Grimaldi; David Proctor; Paul Thompson (European Journal of Applied Physiology, 2011)

A Real-Time Risk Assessment Tool Supporting Wildland Fire Decisionmaking - David E. Calkin; Matthew P. Thompson; Mark A. Finney; Kevin D. Hyde (Journal of Forestry, 2011)
Development of appropriate management strategies for escaped wildland fires is complex. Fire managers need the ability to identify, in real time, the likelihood that wildfire will affect valuable developed and natural resources (e.g., private structures, public infrastructure, and natural and cultural resources). These determinations help guide where and when aggressive suppression is required to protect values and when fire may be allowed to burn to enhance ecosystem conditions. This article describes the primary components of the Wildland Fire Decision Support System (WFDSS), a geospatial decision support system developed by the US Forest Service. WFDSS provides state-of-the-art wildfire risk analysis, decision documentation, and long-term implementation planning. In particular, we describe how the two primary decision support analysis components of WFDSS, Fire Spread Probability (fire behavior) and Rapid Assessment of Values at Risk (resource assessment), fit into the current state of risk assessment tools for wildfire suppression decisionmaking.

Oxidative stress, inflammation and recovery of muscle function after damaging exercise: effect of 6-week mixed antioxidant supplementation - David M. Bailey; Clyde Williams; James A. Betts; Dylan Thompson; Tina L. Hurst (European Journal of Applied Physiology, 2011)

Genes in the insulin and insulin-like growth factor pathway and odds of metachronous colorectal neoplasia - Elizabeth C. LeRoy; Jason H. Moore; Chengcheng Hu; María Elena Martínez; Peter Lance; David Duggan; Patricia A. Thompson (Human Genetics, 2011)

Habitat and conservation of the enigmatic damselfly Ischnura pumilio - Katherine A. Allen; Mike G. Le Duc; David J. Thompson (Journal of Insect Conservation, 2010)

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Effect of Different Genotypes of Phytophthora infestans (Mont. de Bary) and Temperature on Tuber Disease Development - William W. Kirk; Alejandro Rojas; Pavani G. Tumbalam; Esther Gachango; Phillip S. Wharton; Firas Abu El-Samen; David Douches; Joseph Coombs; Christian Thill; Asunta Thompson (American Journal of Potato Research, 2010)

Trait similarity, shared ancestry and the structure of neighbourhood interactions in a subtropical wet forest: implications for community assembly - María Uriarte; Nathan G. Swenson; Robin L. Chazdon; Liza S. Comita; W. John Kress; David Erickson; Jimena Forero‐Montaña; Jess K. Zimmerman; Jill Thompson (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1503–1514 Abstract The phylogenetic structure and distribution of functional traits in a community can provide insights into community assembly processes. However, these insights are sensitive to the spatial scale of analysis. Here, we use spatially explicit, neighbourhood models of tree growth and survival for 19 tree species, a highly resolved molecular phylogeny and information on eight functional traits to quantify the relative efficacy of functional similarity and shared ancestry in describing the effects of spatial interactions between tree species on demographic rates. We also assess the congruence of these results with observed phylogenetic and functional structure in the neighbourhoods of live and dead trees. We found strong support for models in which the effects of spatial neighbourhood interactions on tree growth and survival were scaled to species‐specific mean functional trait values (e.g., wood specific gravity, leaf succulence and maximum height) but not to phylogenetic distance. The weak phylogenetic signal in functional trait data allowed us to independently interpret the static neighbourhood functional and phylogenetic patterns. We observed greater functional trait similarity in the neighbourhoods of live trees relative to those of dead trees suggesting that environmental filtering is the major force structuring this tree community at this scale while competitive interactions play a lesser role.

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Patterns of spatial genetic structure and diversity at the onset of a rapid range expansion: colonisation of the UK by the small red-eyed damselfly Erythromma viridulum - Phillip C. Watts; Simon Keat; David J. Thompson (Biological Invasions, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

The dragonfly delusion: why it is essential to sample exuviae to avoid biased surveys - Eva M. Raebel; Thomas Merckx; Philip Riordan; David W. Macdonald; David J. Thompson (Journal of Insect Conservation, 2010)

Novel quantitative trait loci for central corneal thickness identified by candidate gene analysis of osteogenesis imperfecta genes - David P. Dimasi; Jern Y. Chen; Alex W. Hewitt; Sonja Klebe; Richard Davey; John Stirling; Elizabeth Thompson; Robin Forbes; Tiong Y. Tan; Ravi Savarirayan; David A. Mackey; Paul R. Healey; et al. (Human Genetics, 2010)

The impact of climate-induced distributional changes on the validity of biological water quality metrics - Christopher Hassall; David J. Thompson; Ian F. Harvey (Environmental Monitoring and Assessment, 2010)

Estimates of the air quality benefits of using natural gas in industrial and transportation applications in Lima, Peru - Tammy Thompson; Yosuke Kimura; Cyril Durrenberger; Alba Webb; Ana Isabel Tejela Matias; Matt Fraser; David T. Allen (Clean Technologies and Environmental Policy, 2009)

Isolation and characterization of microsatellite loci from the invasive delicate skink (Lampropholis delicata), with cross-amplification in other Australian Eugongylus group species - David G. Chapple; Michael B. Thompson (Conservation Genetics Resources, 2009)

Monash at the academic industrial interface: trains and platforms - Alexander Ian Smith; Phillip R. Thompson; David P. Gearing (Journal of Molecular Medicine, 2009)

Erratum to: Characterizing the Relative Contributions of Large Vessels to Total Ocean Noise Fields: A Case Study Using the Gerry E. Studds Stellwagen Bank National Marine Sanctuary - Leila Hatch; Christopher Clark; Richard Merrick; Sofie Van Parijs; Dimitri Ponirakis; Kurt Schwehr; Michael Thompson; David Wiley (Environmental Management, 2009)

Reproductive timing and patterns of development for the damselfly Coenagrion puella in the field - Chris D. Lowe; Ian F. Harvey; Phillip C. Watts; David J. Thompson (Ecology, 2009)
By a combination of detailed behavioral observations and molecular genetic approaches we have assessed development time, timing of first maturity, and the extent of genetic structure through the flying season in a wild population of the damselfly Coenagrion puella in England. This work provides the first estimate of development time (egg to mature adult) in the field based on individual damselflies. Development time was significantly longer for females than males. In contrast to reported laboratory studies, there was no difference in development times between different female color morphs. Development time ranged between 347 and 396 days and was negatively correlated with egg‐laying date. As a result eggs laid early in one season reach adult maturity relatively late in the next; concurrently individuals developing from eggs laid late mature relatively early. We speculate that this pattern of development is a direct physiological response to seasonal environmental variation and results in reproductive synchrony within a population. Size, specifically hind wing length, declined with development time in males, but not in females. In one of the two years of the study there was evidence for weak clustering of related individuals during the reproductive season. This appeared to be the result of developmental synchronization within families: variance in timing of maturation was smaller in full‐sib families than in half‐sib families or randomly assigned unrelated groups.

Impact of Different US Genotypes of Phytophthora infestans on Potato Seed Tuber Rot and Plant Emergence in a Range of Cultivars and Advanced Breeding Lines - William W. Kirk; Firas Abu-El Samen; Pavani Tumbalam; Phillip Wharton; David Douches; Christian A. Thill; Asunta Thompson (Potato Research, 2009)

Biodiversity Conservation in Local Planning - JAMES R. MILLER; MARTHA GROOM; GEORGE R. HESS; TODDI STEELMAN; DAVID L. STOKES; JAN THOMPSON; TROY BOWMAN; LAURA FRICKE; BRANDON KING; RYAN MARQUARDT (Conservation Biology, 2009)
Local land‐use policy is increasingly being recognized as fundamental to biodiversity conservation in the United States. Many planners and conservation scientists have called for broader use of planning and regulatory tools to support the conservation of biodiversity at local scales. Yet little is known about the pervasiveness of these practices. We conducted an on‐line survey of county, municipal, and tribal planning directors (n = 116 ) in 3 geographic regions of the United States: metropolitan Seattle, Washington; metropolitan Des Moines, Iowa; and the Research Triangle, North Carolina. Our objectives were to gauge the extent to which local planning departments address biodiversity conservation and to identify factors that facilitate or hinder conservation actions in local planning. We found that biodiversity conservation was seldom a major consideration in these departments. Staff time was mainly devoted to development mandates and little time was spent on biodiversity conservation. Regulations requiring conservation actions that might benefit biodiversity were uncommon, with the exception of rules governing water quality in all 3 regions and the protection of threatened and endangered species in the Seattle region. Planning tools that could enhance habitat conservation were used infrequently. Collaboration across jurisdictions was widespread, but rarely focused on conservation. Departments with a conservation specialist on staff tended to be associated with higher levels of conservation actions. Jurisdictions in the Seattle region also reported higher levels of conservation action, largely driven by state and federal mandates. Increased funding was most frequently cited as a factor that would facilitate greater consideration of biodiversity in local planning. There are numerous opportunities for conservation biologists to play a role in improving conservation planning at local scales.

Solid Phase Synthesis and Circular Dichroism Analysis of (i → i + 4) Cyclic Lactam Analogues of Kisspeptin - Michelle A. Camerino; David C. M. Kong; David K. Chalmers; Philip E. Thompson (International Journal of Peptide Research and Therapeutics, 2008)

Meeting the Challenges of Neuroimaging Genetics - Greig I. de Zubicaray; Ming-Chang Chiang; Katie L. McMahon; David W. Shattuck; Arthur W. Toga; Nicholas G. Martin; Margaret J. Wright; Paul M. Thompson (Brain Imaging and Behavior, 2008)

External Human Factors in Incident Management Team Decisionmaking and Their Effect on Large Fire Suppression Expenditures - Janie Canton-Thompson; Krista M. Gebert; Brooke Thompson; Greg Jones; David Calkin; Geoff Donovan (Journal of Forestry, 2008)
Large wildland fires are complex, costly events influenced by a vast array of physical, climatic, and social factors. Changing climate, fuel buildup due to past suppression, and increasing populations in the wildland-urban interface have all been blamed for the extreme fire seasons and rising suppression expenditures of recent years. With each high-cost year comes a multitude of fire cost reviews, suppression cost studies by federal oversight agencies, and new rules and regulations focused on containing or reducing suppression costs. However, largely ignored in many of these inquiries are the human factors and pressures outside (external to) the influence of the incident team managing a fire that are contributing to the problem. This article presents an in-depth examination of some external human factors that affect incident management team (IMT) decisionmaking and influence suppression costs. Data were collected during 2004 and 2005 through 48 in-depth interviews with IMT command and general staff members representative of each Geographic Area Coordination Center, all federal agencies, and many state agencies whose employees serve on teams. External human factors identified include risk management; interaction with agency administrators; policies, regulations, and rules; resource availability; and social-political pressure. Inattention to these factors can result in policies that adversely affect IMTs charged with managing highly volatile events in a safe, timely, and cost-efficient manner.

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part II: future estimates - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part I: historical analysis - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Characterizing the Relative Contributions of Large Vessels to Total Ocean Noise Fields: A Case Study Using the Gerry E. Studds Stellwagen Bank National Marine Sanctuary - Leila Hatch; Christopher Clark; Richard Merrick; Sofie Van Parijs; Dimitri Ponirakis; Kurt Schwehr; Michael Thompson; David Wiley (Environmental Management, 2008)

Heterologous expression of pyruvate decarboxylase in Geobacillus thermoglucosidasius - Ann H. Thompson; David J. Studholme; Edward M. Green; David J. Leak (Biotechnology Letters, 2008)

Strong genetic divergence indicates that congeneric damselflies Coenagrion puella and C. pulchellum (Odonata: Zygoptera: Coenagrionidae) do not hybridise - Chris D. Lowe; Ian F. Harvey; David J. Thompson; Phillip C. Watts (Hydrobiologia, 2008)

Characterisation of the Bax-nucleophosmin interaction: the importance of the Bax C-terminus - Jane Thompson; Keith Finlayson; Eliane Salvo-Chirnside; David MacDonald; James McCulloch; Lorraine Kerr; John Sharkey (Apoptosis, 2008)

Elk browsing increases aboveground growth of water-stressed willows by modifying plant architecture - Danielle B. Johnston; David J. Cooper; N. Thompson Hobbs (Oecologia, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Does size matter for dispersal distance? - David G. Jenkins; Camille R. Brescacin; Craig V. Duxbury; Jennifer A. Elliott; Jennafer A. Evans; Katherine R. Grablow; Melissa Hillegass; Boyd N. Lyon; Genevieve A. Metzger; Michelle L. Olandese; Diana Pepe; Greg A. Silvers; et al. (Global Ecology and Biogeography, 2007)
Aim The aim of this study is to answer the questions: (1) do small organisms disperse farther than large, or vice versa; and (2) does the observed pattern differ for passive and active dispersers? These questions are central to several themes in biogeography (including microbial biogeography), macroecology, metacommunity ecology and conservation biology. Location The meta‐analysis was conducted using published data collected worldwide. Methods We collected and analysed 795 data values in the peer‐reviewed literature for direct observations of both maximal dispersal distance and mass of the dispersing organisms (e.g. seeds, not trees). Analysed taxa ranged in size from bacteria to whales. We applied macroecology analyses based on null models (using Monte Carlo randomizations) to test patterns relative to specific hypotheses. Results Collected dispersal distance and mass data spanned 9 and 21 orders of magnitude, respectively. Active dispersers dispersed significantly farther ( P P Conclusions Size is important to maximal dispersal distance for active dispersers, but not for passive dispersers. Claims that microbes disperse widely cannot be tested by current data based on direct observations of dispersal: indirect approaches will need to be applied. Distance–mass relationships should contribute to a resolution of neutral and niche‐based metacommunity theories by helping scale expectations for dispersal limitation. Also, distance–mass relationships should inform analyses of latitudinal species richness and conservation biology topics such as fragmentation, umbrella species and taxonomic homogenization.

Private Native Forestry in NSW: Environmentally Benign, Economically Important but Silviculturally Challenged? - David Thompson (Small-scale Forestry, 2007)

History of diabetes mellitus and subsequent prostate cancer risk in the NIH-AARP Diet and Health Study - Brook A. Calton; Shih Chen Chang; Margaret E. Wright; Victor Kipnis; Karla Lawson; Frances E. Thompson; Amy F. Subar; Traci Mouw; David S. Campbell; Paul Hurwitz; Albert Hollenbeck; Arthur Schatzkin; et al. (Cancer Causes & Control, 2007)

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)
Responses of biota to climate change take a number of forms including distributional shifts, behavioural changes and life history changes. This study examined an extensive set of biological records to investigate changes in the timing of life history transitions (specifically emergence) in British Odonata between 1960 and 2004. The results show that there has been a significant, consistent advance in phenology in the taxon as a whole over the period of warming that is mediated by life history traits. British odonates significantly advanced the leading edge (first quartile date) of the flight period by a mean of 1.51 ±0.060 (SEM, n =17) days per decade or 3.08±1.16 (SEM, n =17) days per degree rise in temperature when phylogeny is controlled for. This study represents the first review of changes in odonate phenology in relation to climate change. The results suggest that the damped temperature oscillations experienced by aquatic organisms compared with terrestrial organisms are sufficient to evoke phenological responses similar to those of purely terrestrial taxa.

How useful is DNA extracted from the legs of archived insects for microsatellite-based population genetic analyses? - Phillip C. Watts; David J. Thompson; Katherine A. Allen; Stephen J. Kemp (Journal of Insect Conservation, 2007)

Roosting site selection in the endangered damselfly, Coenagrion mercuriale, and implications for habitat design - James R. Rouquette; David J. Thompson (Journal of Insect Conservation, 2007)

Dihydroxyoctadecamonoenoate esters inhibit the neutrophil respiratory burst - David Alan Thompson; Bruce D Hammock (Journal of Biosciences, 2007)

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)

Compatible genetic and ecological estimates of dispersal rates in insect ( Coenagrion mercuriale : Odonata: Zygoptera) populations: analysis of ‘neighbourhood size’ using a more precise estimator - PHILLIP C. WATTS; FRANÇOIS ROUSSET; ILIK J. SACCHERI; RAPHAËL LEBLOIS; STEPHEN J. KEMP; DAVID J. THOMPSON (Molecular Ecology, 2007)
Genetic and demographic estimates of dispersal are often thought to be inconsistent. In this study, we use the damselfly Coenagrion mercuriale (Odonata: Zygoptera) as a model to evaluate directly the relationship between estimates of dispersal rate measured during capture–mark–recapture fieldwork with those made from the spatial pattern of genetic markers in linear and two‐dimensional habitats. We estimate the ‘neighbourhood size’ ( Nb ) — the product of the mean axial dispersal rate between parent and offspring and the population density — by a previously described technique, here called the regression method. Because C. mercuriale is less philopatric than species investigated previously by the regression method we evaluate a refined estimator that may be more applicable for relatively mobile species. Results from simulations and empirical data sets reveal that the new estimator performs better under most situations, except when dispersal is very localized relative to population density. Analysis of the C. mercuriale data extends previous results which demonstrated that demographic and genetic estimates of Nb by the regression method are equivalent to within a factor of two at local scales where genetic estimates are less affected by habitat heterogeneity, stochastic processes and/or differential selective regimes. The corollary is that with a little insight into a species’ ecology the pattern of spatial genetic structure provides quantitative information on dispersal rates and/or population densities that has real value for conservation management.

Hurricanes 2004: An overview of their characteristics and coastal change - Asbury H. Sallenger; Hilary F. Stockdon; Laura Fauver; Mark Hansen; David Thompson; C. Wayne Wright; Jeff Lillycrop (Estuaries and Coasts, 2006)

Fracture in Westerly Granite under AE Feedback and Constant Strain Rate Loading: Nucleation, Quasi-static Propagation, and the Transition to Unstable Fracture Propagation - Ben D. Thompson; R. Paul Young; David A. Lockner (Pure and Applied Geophysics, 2006)

Cell and tissue responses of a range of Urotensin II analogs at cloned and native urotensin II receptors. Evidence for coupling promiscuity - Wei Song; John McDonald; Valeria Camarda; Girolamo Calo; Remo Guerrini; Erika Marzola; Jonathan P. Thompson; David J. Rowbotham; David G. Lambert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Demographic and Female Life History Parameters of Free-Ranging Chimpanzees at the Chimpanzee Rehabilitation Project, River Gambia National Park - Stella Brewer Marsden; David Marsden; Melissa Emery Thompson (International Journal of Primatology, 2006)

A stable isotopic investigation into the causes of decline in a sub‐Antarctic predator, the rockhopper penguin Eudyptes chrysocome - GEOFF M. HILTON; DAVID R. THOMPSON; PAUL M. SAGAR; RICHARD J. CUTHBERT; YVES CHEREL; SARAH J. BURY (Global Change Biology, 2006)
The rockhopper penguin ( Eudyptes chrysocome ) is a conspicuous apex marine predator that has experienced marked population declines throughout most of its circumpolar breeding distribution. The cause(s) for the declines remain elusive, but the relatively large spatio‐temporal scale over which population decreases have occurred implies that ecosystem‐scale, at‐sea factors are likely to be involved. We employ stable isotope analyses of carbon ( 13 C/ 12 C, expressed as δ 13 C) and nitrogen ( 15 N/ 14 N, δ 15 N) in time‐series of rockhopper penguin feather samples, dating back to 1861, in order to reconstruct the species' ecological history. Specifically, we examine whether rockhopper penguin population decline has been associated with a shift towards lower primary productivity in the ecosystem in which they feed, or with a shift to a diet of lower trophic status and lower quality, and we use long‐term temperature records to evaluate whether shifts in isotope ratios are associated with annual variations in sea surface temperature. Having controlled temporally for the Suess Effect and for increases in CO 2 concentrations in seawater, we found that overall, δ 13 C signatures decreased significantly over time in rockhopper penguins from seven breeding sites, supporting the hypothesis that decreases in primary productivity, and hence, carrying capacity, for which δ 13 C signature is a proxy, have been associated with the decline of penguin populations. There was some evidence of a long‐term decline in δ 15 N at some sites, and strong evidence that δ 15 N signatures were negatively related to sea surface temperatures across sites, indicative of a shift in diet to prey of lower trophic status over time and in warm years. However, a site‐by‐site analysis revealed divergent isotopic trends among sites: five of seven sites exhibited significant temporal or temperature‐related trends in isotope signatures. This study highlights the utility of stable isotope analyses when applied over relatively long timescales to apex predators.

Songbirds using crops planted on farmland as cover for game birds - Rufus B. Sage; David M. B. Parish; Maureen I. A. Woodburn; Peter G. L. Thompson (European Journal of Wildlife Research, 2005)

The Effects of Four Insect Growth-Regulating (IGR) Insecticides on Honeybee (Apis mellifera L.) Colony Development, Queen Rearing and Drone Sperm Production - Helen M. Thompson; Selwyn Wilkins; Alastair H. Battersby; Ruth J. Waite; David Wilkinson (Ecotoxicology, 2005)

Stable isotopes in ecological studies - David R. Thompson; Sarah J. Bury; Keith A. Hobson; Leonard I. Wassenaar; Joseph P. Shannon (Oecologia, 2005)

Localization of infaunal prey by the sea star Leptasterias polaris - Myles Thompson; David Drolet; John H. Himmelman (Marine Biology, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Parallel influence of climate on the behaviour of Pacific killer whales and Atlantic bottlenose dolphins - David Lusseau; Rob Williams; Ben Wilson; Kate Grellier; Tim R. Barton; Philip S. Hammond; Paul M. Thompson (Ecology Letters, 2004)
The grouping behaviour of animals is governed by intrinsic and extrinsic factors which play an important role in shaping their social organization. We investigated the influence of ocean climate variation on the grouping behaviour of two widely separated populations of cetaceans, inhabiting north Atlantic and north Pacific coastal waters. The group size of both bottlenose dolphins in the Moray Firth, UK, and killer whales in Johnstone Strait, Canada, varied from year to year in relation to large‐scale ocean climate variation. Local indices of prey abundance were also related both to climate indices and predator group sizes. The cetaceans tended to live in smaller groups when there was less salmon available in both areas which seem to occur 2 years after a lower phase of the North Atlantic and Pacific Decadal Oscillations. These findings suggest that, even in highly social mammals, climate variation may influence social organization through changes in prey availability.

Simulating the Effect of Landscape Size and Age Structure on Cavity Tree Density Using a Resampling Technique - Zhaofei Fan; Stephen S. Lee; Stephen R. Shifley; Frank R. Thompson III; David R. Larsen (Forest Science, 2004)
Cavity-tree density (CTD) is an important indicator of habitat quality for cavity-dependent wildlife. However, the abundance of cavities and cavity trees can vary dramatically, even among trees or stands with similar attributes. This uncertainty can make it difficult to expand stand-levelestimates of cavity abundance to large landscapes, although it is often desirable to do so. This limits the utility of CTD as a measure of habitat quality. We use a resampling method (statistical bootstrap) to construct a set of regression models to predict CTD based on landscape age structureand landscape size. The estimated regression coefficients are highly variable (in terms of the adjusted R2 and root mean square error) for landscapes <100 ha, but the models perform well for larger landscapes. We test the regression models using an independent data set from theMissouri Ozark Forest Ecosystem Project (MOFEP) and find that the mean relative error (RE) when predicting CTD for landscapes between 300 and 4,000 ha is less than 10%. Both the size (in hectares) of the landscape and the stand age-class components affect RE; but RE decreases with increasinglandscape size in a consistent and quantifiable manner. For Ozark landscapes ≥100 ha, knowledge of the proportion of the area in the seedling/sapling, pole, sawtimber, and old-growth age classes can be used to readily estimate the number of cavity trees and how that number will change ifthe landscape age structure is altered. FOR. SCI. 50(5):603–609.

Remote sensing of upland vegetation: the potential of high spatial resolution satellite sensors - Henny Mehner; Mark Cutler; David Fairbairn; Gillian Thompson (Global Ecology and Biogeography, 2004)
Aim Traditional methodologies of mapping vegetation, as carried out by ecologists, consist primarily of field surveying or mapping from aerial photography. Previous applications of satellite imagery for this task (e.g. Landsat TM and SPOT HRV) have been unsuccessful, as such imagery proved to have insufficient spatial resolution for mapping vegetation. This paper reports on a study to assess the capabilities of the recently launched remote sensing satellite sensor Ikonos, with improved capabilities, for mapping and monitoring upland vegetation using traditional image classification methods. Location The location is Northumberland National Park, UK. Methods Traditional remote sensing classification methodologies were applied to the Ikonos data and the outputs compared to ground data sets. This enabled an assessment of the value of the improved spatial resolution of satellite imagery for mapping upland vegetation. Post‐classification methods were applied to remove noise and misclassified pixels and to create maps that were more in keeping with the information requirements of the NNPA for current management processes. Results The approach adopted herein for quick and inexpensive land cover mapping was found to be capable of higher accuracy than achieved with previous approaches, highlighting the benefits of remote sensing for providing land cover maps. Main conclusions Ikonos imagery proved to be a useful tool for mapping upland vegetation across large areas and at fine spatial resolution, providing accuracies comparable to traditional mapping methods of ground surveys and aerial photography.

Empirical modeling of summer lake surface temperatures in southwest Greenland - Helen Kettle; Roy Thompson; N. John Anderson; David M. Livingstone (Limnology and Oceanography, 2004)
This work presents a method to estimate mean daily lake surface water temperatures using only air temperature, theoretical clear‐sky solar radiation, and lake size. Surface water temperatures were measured at a selection of lakes in southwest Greenland during the summers of 1998–2000. The lakes are small (surface area

Physiological responses to intermittent and continuous exercise at the same relative intensity in older men - Norman Morris; Gregory Gass; Martin Thompson; David Conforti (European Journal of Applied Physiology, 2003)

Effects of Land Cover on Stream Ecosystems: Roles of Empirical Models and Scaling Issues - David L. Strayer; R. Edward Beighley; Lisa C. Thompson; Shane Brooks; Christer Nilsson; Gilles Pinay; Robert J. Naiman (Ecosystems, 2003)

Statistical hypothesis testing formulations for U.S. environmental regulatory standards for ozone - Mary Lou Thompson; Lawrence H. Cox; Paul D. Sampson; David C. Caccia (Environmental and Ecological Statistics, 2002)

Formation of Plasmid-Based Transfection Complexes with an Acid-Labile Cationic Lipid: Characterization of in Vitro and in Vivo Gene Transfer - Jeremy A. Boomer; David H. Thompson; Sean M. Sullivan (Pharmaceutical Research, 2002)

Effects of resource quality on the population dynamics of the Indian meal moth Plodia interpunctella and its granulovirus - Ross I. McVean; Steve M. Sait; David J. Thompson; Mike Begon (Oecologia, 2002)

Lifetime Reproductive Success in the Solitary Endoparasitoid, Venturia canescens - Jeffrey A. Harvey; Ian F. Harvey; David J. Thompson (Journal of Insect Behavior, 2001)

The Relationship between the Meridional Profile of Zonal-mean Geostrophic Wind and Station Wave at 500 hPa - Fang Zhifang; John M. Wallace; David W. J. Thompson (Advances in Atmospheric Sciences, 2001)

Modeling Global Climate–Vegetation Interactions in a Doubled CO2 World - Jon C. Bergengren; Starley L. Thompson; David Pollard; Robert M. DeConto (Climatic Change, 2001)

Risedronate Pharmacokinetics and Intra- and Inter-Subject Variability Upon Single-Dose Intravenous and Oral Administration - David Y. Mitchell; William H. Barr; Rachelle A. Eusebio; Karen A. Pallone Stevens; Frank P. Duke; Darrell A. Russell; John D. Nesbitt; James H. Powell; Gary A. Thompson (Pharmaceutical Research, 2001)

GCM-simulated hydrology in the Arctic duringn the past 21,000 years - Benjamin Felzer; Starley Thompson; David Pollard; Jon Bergengren (Journal of Paleolimnology, 2000)

Abscisic acid biosynthesis in tomato: regulation of zeaxanthin epoxidase and 9-cis-epoxycarotenoid dioxygenase mRNAs by light/dark cycles, water stress and abscisic acid - Andrew J. Thompson; Alison C. Jackson; Rachel A. Parker; David R. Morpeth; Alan Burbidge; Ian B. Taylor (Plant Molecular Biology, 2000)

Laboratory Kinetic Studies of the Reactions of Cl Atoms with Species of Biogenic Origin: δ3-Carene, Isoprene, Methacrolein and Methyl Vinyl Ketone - Carlos E. Canosa-Mas; Hilary R. Hutton-Squire; Martin D. King; David J. Stewart; Katherine C. Thompson; Richard P. Wayne (Journal of Atmospheric Chemistry, 1999)

The relationship between diet and breast cancer in men (United States) - Karin A. Rosenblatt; David B. Thomas; L. Margarita Jimenez; Brian Fish; Anne McTiernan; Helge Stalsberg; Annette Stemhagen; W. Douglas Thompson; Mary G. McGrea Curnen; William Satariano; Donald F. Austin; Raymond S. Greenberg; et al. (Cancer Causes & Control, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Selective Stimulation of Latissimus Dorsi Muscle for Cardiac Assist - Dirk R. Thompson; John J. Michele; Erik A. Cheever; David T. George (Annals of Biomedical Engineering, 1999)

Unequal competitor ideal free distribution in fish? - Tom Tregenza; David J. Thompson (Evolutionary Ecology, 1998)

Coupling dynamic models of climate and vegetation - JONATHAN A. FOLEY; SAMUEL LEVIS; COLIN I. PRENTICE; DAVID POLLARD; STARLEY L. THOMPSON (Global Change Biology, 1998)

Coupling dynamic models of climate and vegetation - Jonathan A. Foley; Samuel Levis; I. Colin Prentice; David Pollard; Starley L. Thompson (Global Change Biology, 1998)
Numerous studies have underscored the importance of terrestrial ecosystems as an integral component of the Earth's climate system. This realization has already led to efforts to link simple equilibrium vegetation models with Atmospheric General Circulation Models through iterative coupling procedures. While these linked models have pointed to several possible climate–vegetation feedback mechanisms, they have been limited by two shortcomings: (i) they only consider the equilibrium response of vegetation to shifting climatic conditions and therefore cannot be used to explore transient interactions between climate and vegetation; and (ii) the representations of vegetation processes and land‐atmosphere exchange processes are still treated by two separate models and, as a result, may contain physical or ecological inconsistencies. Here we present, as a proof concept, a more tightly integrated framework for simulating global climate and vegetation interactions. The prototype coupled model consists of the GENESIS (version 2) Atmospheric General Circulation Model and the IBIS (version 1) Dynamic Global Vegetation Model. The two models are directly coupled through a common treatment of land surface and ecophysiological processes, which is used to calculate the energy, water, carbon, and momentum fluxes between vegetation, soils, and the atmosphere. On one side of the interface, GENESIS simulates the physics and general circulation of the atmosphere. On the other side, IBIS predicts transient changes in the vegetation structure through changes in the carbon balance and competition among plants within terrestrial ecosystems. As an initial test of this modelling framework, we perform a 30 year simulation in which the coupled model is supplied with modern CO 2 concentrations, observed ocean temperatures, and modern insolation. In this exploratory study, we run the GENESIS atmospheric model at relatively coarse horizontal resolution (4.5° latitude by 7.5° longitude) and IBIS at moderate resolution (2° latitude by 2° longitude). We initialize the models with globally uniform climatic conditions and the modern distribution of potential vegetation cover. While the simulation does not fully reach equilibrium by the end of the run, several general features of the coupled model behaviour emerge. We compare the results of the coupled model against the observed patterns of modern climate. The model correctly simulates the basic zonal distribution of temperature and precipitation, but several important regional biases remain. In particular, there is a significant warm bias in the high northern latitudes, and cooler than observed conditions over the Himalayas, central South America, and north‐central Africa. In terms of precipitation, the model simulates drier than observed conditions in much of South America, equatorial Africa and Indonesia, with wetter than observed conditions in northern Africa and China. Comparing the model results against observed patterns of vegetation cover shows that the general placement of forests and grasslands is roughly captured by the model. In addition, the model simulates a roughly correct separation of evergreen and deciduous forests in the tropical, temperate and boreal zones. However, the general patterns of global vegetation cover are only approximately correct: there are still significant regional biases in the simulation. In particular, forest cover is not simulated correctly in large portions of central Canada and southern South America, and grasslands extend too far into northern Africa. These preliminary results demonstrate the feasibility of coupling climate models with fully dynamic representations of the terrestrial biosphere. Continued development of fully coupled climate‐vegetation models will facilitate the exploration of a broad range of global change issues, including the potential role of vegetation feedbacks within the climate system, and the impact of climate variability and transient climate change on the terrestrial biosphere.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Ten Guidelines for Ecosystem Researchers: Lessons from Missouri - David R. Larsen; Stephen R. Shifley; Frank R. Thompson III; Brian L. Brookshire; Daniel C. Dey; Eric W. Kurzejeski; Kristine England (Journal of Forestry, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Mutation detection in FGFR2 craniosynostosis syndromes - G. E. Hollway; Graeme K. Suthers; Eric A. Haan; Elizabeth Thompson; David J. David; Jozef Gecz; John C. Mulley (Human Genetics, 1997)

Tissue antioxidant status in streptozotocin-induced diabetes in rats - Katherine H. Thompson; David V. Godin; Melvin Lee (Biological Trace Element Research, 1992)

Armed sibling rivalry among suckling piglets - David Fraser; B. K. Thompson (Behavioral Ecology and Sociobiology, 1991)

High altitude echolocation of insects by bats - Donald R. Griffin; David Thompson (Behavioral Ecology and Sociobiology, 1982)

Echolocation by cave swiftlets - Donald R. Griffin; David Thompson (Behavioral Ecology and Sociobiology, 1982)

Flight speeds of birds observed with radar: Evidence for two phases of migratory flight - Ronald P. Larkin; David Thompson (Behavioral Ecology and Sociobiology, 1980)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)